Negative electrode material precursor and preparation method thereof, negative electrode material, electrochemical device and electronic device

By using a negative electrode material precursor with low crystalline carbon content, silicon-carbon composite negative electrode material with high particle strength and surface stability was prepared, which solved the problem of volume expansion of silicon-based negative electrode material in lithium-ion batteries and significantly improved the cycling and rate performance of the battery.

CN119911903APending Publication Date: 2025-05-02SHANGHAI NANOMET TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411673981.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The volume expansion of the silicon-based negative electrode material in lithium-ion batteries during lithium embedding is severe, resulting in poor circulation performance, low first-time efficiency, poor rate performance, and inability to meet the needs of large-scale applications.

Method used

A silicon-carbon composite anode material with high particle strength and surface stability was prepared by a gas activation method and a alkali activation method. The carbon Raman peak Id/Ig ratio of this material is between 0.7 and 1.7, and the particle size is uniform. The BET value is between 1000-4000m2/g. The GM value is 12-32. The proportion of silicon elements is 0.001%-5%, the proportion of carbon elements is 70%-100%, and the proportion of oxygen elements is 0.1%-10%.

Benefits of technology

It significantly alleviates the expansion and contraction of lithium ions embedded and detached, reduces the capacity reduction caused by surface SEI repair, improves the particle strength and surface stability of the battery, and improves the theoretical capacity, cycle retention rate and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911903A_ABST
    Figure CN119911903A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material precursor and a preparation method thereof, a negative electrode material, a secondary battery and an electronic device. A precursor Dv50 of the negative electrode material is 3-15 [mu] m, Dv99 is 6-30 [mu] m, and Dn10 and Dv10 meet the following relation: 0.1 < = Dn10 / Dv10 < = 0.9; the sphericity degree of the precursor particles of the negative electrode material is preferably 50-97%. The negative electrode material precursor provided by the invention comprises low-crystallinity carbon, and the carbon Raman peak Id / Ig ratio is 0.7-1.7; the mass ratio range of the silicon element of the cathode material precursor is more than or equal to 0.001% and less than or equal to 5%, the mass ratio range of the carbon element is more than or equal to 70% and less than 100%, and the mass ratio of the oxygen element is 0.1-10%. The negative electrode material precursor provided by the invention has a low closed hole area ratio gt; the area ratio of a 100 nm closed hole is 1t; 20%; the negative electrode material precursor has a high BET value of 1000 to 4000 and a high GM value (12 to 32); the silicon-carbon composite negative electrode material adopting the negative electrode material precursor greatly improves the expansion, cycling stability and rate capability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, in particular to the field of lithium-ion battery technology, and specifically to a negative electrode material precursor and a preparation method thereof, a negative electrode material, a secondary battery and an electronic device. Background Art

[0002] As the power of electrical devices such as mobile phones, computers, electric vehicles, and energy storage power stations continues to increase, people's requirements for the energy density of lithium batteries are also increasing. At present, silicon as a negative electrode material for lithium-ion batteries has a theoretical capacity of up to 4200mAh / g, which is much higher than the theoretical capacity of graphite, a commercial negative electrode material, 372mAh / g. Therefore, it is considered The industry has begun to add silicon-based negative electrode materials to the negative electrode, which can significantly improve the energy density of the battery. However, during the lithium insertion process, the silicon-based negative electrode will undergo a huge volume expansion (300-400%), resulting in poor cycle performance, low initial efficiency, poor rate, and other problems. Currently, it cannot meet the needs of large-scale applications. To solve this problem, silicon-carbon anode is the most promising material among silicon-based anodes; the current method is to deposit nano-silicon inside porous carbon and use the reserved gaps inside the porous carbon to reduce the expansion rate of the silicon anode. However, during the charge and discharge process, the material particles are constantly expanding and contracting, resulting in the appearance of new electrolyte / active material interfaces on the particle surface, especially nano-silicon. Silicon has a higher reactivity with electrolytes, which will continuously consume electrolytes to form unstable solid electrolyte membranes (SEI membranes), which can easily lead to irreversible lithium consumption and poor conductive networks, resulting in rapid battery capacity decay and rate performance degradation. Existing technologies for improving silicon-carbon negative electrodes cannot significantly improve battery cycle and rate performance. The present invention has found that the precursor of silicon-carbon negative electrode material is closely related to the particle structure strength and surface activity, and the particle strength and surface activity have a great influence on the electrolyte consumption and battery expansion, cycle and rate performance. Summary of the invention

[0003] To solve the above problems, the present invention provides a negative electrode material precursor for lithium ion secondary batteries, a silicon-carbon composite negative electrode material, a negative electrode for lithium ion secondary batteries, and a lithium ion secondary battery with small expansion, high specific capacity, and excellent cycle and rate.

[0004] The present invention provides a method for preparing a silicon-carbon composite negative electrode material precursor, which has a simple process and is suitable for industrial production. The present invention provides a silicon-carbon composite negative electrode material with high particle strength and strong surface stability. The present invention provides a lithium-ion battery with excellent expansion, cycle and rate performance.

[0005] The invention provides an electronic device.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical scheme is specially adopted: A first aspect of the present invention provides a negative electrode material precursor, which comprises low-crystalline carbon, and the carbon Raman peak Id / Ig ratio is 0.7 to 1.7; the negative electrode material precursor is characterized in that: 1) The Dv50 of the negative electrode material precursor is 3μm to 15μm, the Dv99 is 6μm to 30μm, and the Dn10 and Dv10 satisfy the following relationship: 0.1≤Dn10 / Dv10≤0.9 2) The negative electrode material precursor has a high BET of 1000-4000 and a high GM value of 12-32; 3) The mass percentage of silicon in the negative electrode material precursor is in the range of 0.001%≤X≤5%, the mass percentage of carbon is in the range of 70%≤Y<100%, and the mass percentage of oxygen is 0.1%-10%; Due to these excellent structural characteristics, the negative electrode material prepared from the negative electrode material precursor of the present invention can alleviate the expansion and contraction caused by the insertion and extraction of lithium ions, and can also reduce the capacity reduction caused by the surface SEI repair per unit volume. Therefore, the negative electrode material has high particle strength and surface stability, a high theoretical capacity of 600-2500 mAh / g, and greatly improves the battery's expansion, cycle retention rate and rate performance; In some embodiments, the negative electrode material precursor has a low crystalline carbon structure, and the carbon Raman peak Id / Ig ratio is 0.7 to 1.7. The carbon Raman peak Id / Ig ratio reflects the degree of carbon disorder. If the ratio is too high, the carbon disorder increases, which is not conducive to the reversible capacity. If it is too low, the degree of graphitization increases, which reduces the strength of the negative electrode material precursor support, which is not conducive to the improvement of particle stability and cycle performance; therefore, too high or too low Raman peak ratios are not conducive to improving energy density or the cycle performance of secondary batteries.

[0007] In some embodiments, the carbon Raman peak Id / Ig ratio is calculated from the Raman spectrum of the negative electrode material precursor to be located at ~1340 cm -1 and ~1600cm -1 Intensity ratio of nearby peaks, light source is 532nm, test wavelength range is 0cm -1 ~4000cm -1. This intensity ratio reflects the degree of disorder of the carbon material, and a higher ratio represents the presence of a higher degree of disordered carbon. In addition, the degree of disorder of the carbon in the negative electrode material precursor can also be confirmed by the presence of a broad peak of carbon near 22° in the X-ray diffraction spectrum, or by other methods, such as using a transmission electron microscope to observe the presence of carbon in the negative electrode material precursor.

[0008] In some embodiments, the particle size Dv50 of the above-mentioned negative electrode material precursor is 3μm to 15μm. In some embodiments, Dv99 is 6μm to 30μm. In some embodiments, Dn10 and Dv10 satisfy the following relationship, 0.1≤Dn10 / Dv10≤0.9. When the Dn10 / Dv10 value of the particle is less than 0.1, the particle distribution is wide, and there are too large or too small particles. When the particle size is too small, the BET of the prepared composite negative electrode material has an increased risk, increasing the contact area with the electrolyte, thereby increasing the side reaction of the composite negative electrode material and the electrolyte, consuming the limited reversible lithium in the battery, and being not conducive to the secondary battery cycle performance; if the particle size is too large, it will increase the diffusion path of lithium ions and increase concentration polarization, which is not conducive to the secondary battery rate performance; when the Dn10 / Dv10 value of the negative electrode material precursor particle is greater than 0.9, the yield is low, the cost is high, and it is difficult to apply it on a large scale commercially.

[0009] In some embodiments, the BET of the negative electrode material precursor is 1000-4000m 2 / g, pore volume is 0.4-2.0cc / g, too low BET, pore volume can load less silicon-containing material, gram capacity is not significantly improved, and the energy density of secondary batteries is not significantly improved. Too high BET, pore volume can load more silicon-containing material, but the strength of the particles is at risk of reduction, and there is a risk of rupture during the cold pressing of the pole piece, which is not conducive to the improvement of the cycle performance of the secondary battery. The ratio of BET to pore volume is GM, ranging from 12-32. GM reflects the pore size distribution. When the ratio is too low, the pore size distribution is too large, and the uniformity of the deposited silicon is also at risk of deterioration. There is a risk of increased stress concentration during lithium extraction, which is not conducive to the improvement of particle stability; too high GM value, the pore distribution is too concentrated, slightly larger pores are less, which is not conducive to the entry of silicon-containing materials into the pores, and silicon-containing materials are easily enriched on the surface, so there is a risk of secondary battery expansion and reduced cycle performance.

[0010] In some embodiments, the mass proportion of carbon in the above-mentioned negative electrode material precursor is 70%-100%, the mass proportion of silicon is 0.001%-5%, and the mass proportion of oxygen is 0.1%-10%. The appropriate proportion of silicon and oxygen is conducive to the entry of silicon-containing materials into the carbon carrier. Excessive proportions of silicon and oxygen are not conducive to the improvement of the gram capacity and conductivity of silicon-carbon composite negative electrode materials, and there is a risk of reducing energy density and rate performance. The mass proportions of nitrogen and hydrogen are 0.1%-10% and 0.01%-5% respectively, which is also conducive to guiding silane to enter the pores for deposition.

[0011] In some embodiments, the low crystalline carbon structure in the negative electrode material precursor can be obtained by appropriately adjusting the heat treatment temperature and heat treatment time in the heat treatment described below.

[0012] In some embodiments, the area ratio of closed pores of the above negative electrode material precursor>100nm is C, and its preferred range is C<20%; C is calculated as C=the sum of the pore areas of the 100 nearest neighboring particles with pore diameter d1>100nm / the sum of the areas of the 100 nearest neighboring particles; if C is too large, it means that the higher the internal porosity of the particles, the lower the strength of the particles, and there is a risk of fragmentation during cold pressing of the negative electrode plate, and the expansion and contraction of the particles during the charge and discharge process will also increase the risk of this rupture, thereby posing a risk of deterioration in the cycle performance of the secondary battery. Therefore, C needs to be controlled within a certain range, which is conducive to improving the cycle performance of the battery. The preferred range of C is C<20%.

[0013] In some embodiments, the sphericity of the above-mentioned negative electrode material precursor particles is preferably 50%-97%. This is because too low sphericity (<30%) causes uneven force on the particles, and the risk of particle fragmentation increases during the cold pressing process or lithium extraction. Too high sphericity (>99%) may lead to higher preparation process costs, and the particles are in tangent contact, the effective contact area is reduced, and the risk of particle contact failure increases due to particle expansion or contraction during lithium extraction in the later stage.

[0014] In some embodiments, the conductivity of the negative electrode material precursor powder is 0.001-20S / cm. Too low conductivity is not conducive to improving the battery rate performance. The conductivity of the negative electrode material precursor powder can be appropriately improved by increasing the pyrolysis temperature or time of the carbon source precursor. When the conductivity is too high>20S / cm, the heat treatment temperature is too high, the disorder of the carbon is reduced, and there is a risk of deteriorating the stability of the particles. It is not conducive to improving the cycle performance of the battery.

[0015] In some embodiments, the tap density of the above-mentioned anode material precursor is TD, and the preferred range of TD is 0.1 < TD < 0.8. The powder compaction density is PD, and the preferred range of PD is 0.3 < PD < 1.0. The tap density is related to the volumetric energy density of the battery. A high tap density is beneficial to improving the density of the electrode sheet, and thus beneficial to the improvement of the battery energy density. At the same time, to better buffer the volume expansion of silicon, a certain buffer space needs to be reserved inside the particles, so the tap density cannot be too high; the same is true for the powder compaction density.

[0016] In some embodiments, the thermal weight loss TG of the above-mentioned anode material precursor is 0.5% - 13%. If the thermal weight loss is too low, there are too few groups inside the particles, which is not conducive to the subsequent entry of silane gas into the pores and is not conducive to the silicon deposition process. If the thermal weight loss is too high, during the silane deposition process, the volatile content increases, and the precursor powder adheres in the low-temperature area of the cavity, resulting in an unstable deposition process. A certain water content (mass ratio is 0.1 - 120 mg / g) increases the polarity of the porous carbon precursor and is beneficial to guiding silane into the pores for deposition.

[0017] In some embodiments, the BET of the above-mentioned anode material precursor is 1000 - 4000m 2 / g, the pore volume is 0.4 - 2.0 cc / g, and the proportion of pores with a pore diameter of 0.3 - 2 nm is > 50%. The micropore adsorption potential is high. If the proportion of micropores is too low, it is not conducive to the entry of silane gas into the pores for deposition and is not conducive to the preparation of a silicon-carbon composite anode material with high specific capacity and excellent cycling performance.

[0018] In some embodiments, the composite anode material obtained by depositing silicon on the above-mentioned anode material precursor has a low DQ / DV primary and secondary peak intensity ratio, and its range satisfies the following relationship: DQ / DV primary and secondary peak intensity ratio = (I2 - I3) / (I1 - I3) < 1; on the DQ / DV-V curve, the characteristic peak located at 0.24V - 0.35V is the main peak, and the highest peak intensity in this voltage range is denoted as I1, and the characteristic peak located at 0.38V - 0.45V is the secondary peak, and the highest peak intensity in this voltage range is denoted as I2. The lowest peak intensity between I1 and I2 is denoted as I3. From the publicly available data, different characteristic peaks correspond to different electrochemical reactions. The characteristic peak of I1 represents the maximum value of the de-lithiation reaction of amorphous LixSi, and the characteristic peak of I2 represents the maximum value of the de-lithiation reaction of crystalline Li15Si4. The more de-lithiation reactions, the higher the corresponding peak intensity. Since the formation of Li15Si4 has a very large expansion ratio on the Si lattice, it is not conducive to the stability of the lattice and the stability of the electrolyte. To reduce this adverse reaction, the DQ / DV primary and secondary peak intensity ratio needs to be controlled within a certain range, and the preferred range is < 1. A low primary and secondary peak intensity ratio is beneficial to the improvement of the cycling performance of the composite anode material.

[0019] In some embodiments, the composite negative electrode material obtained after silicon is deposited on the negative electrode material precursor has a low>100nm closed pore area ratio C (C<20%); the calculation method is, C=the sum of the pore areas of the 100 nearest neighboring particles with pore diameter d1>100nm / the sum of the areas of the 100 nearest neighboring particles; if C is too large, it means that the higher the internal porosity of the particles, the lower the strength of the particles, and there is a risk of fragmentation during cold pressing of the negative electrode pole piece, and the expansion and contraction of the particles during the charging and discharging process will also increase the risk of this rupture, thereby posing a risk of deterioration in the cycle performance of the secondary battery. Therefore, C needs to be controlled within a certain range, which is conducive to the improvement of the battery cycle performance. The preferred range of C is, C<20%.

[0020] In some embodiments, the composite negative electrode material obtained after silicon is deposited from the negative electrode material precursor, silicon exists in the porous carbon support, the presence of the carbon support can not only increase the conductivity of the material, but also help to inhibit the volume expansion of silicon, thereby effectively improving the gram capacity (600-2500mAh / g), the first charge and discharge efficiency (2.0V, 80%-96%), and the high 0.9V capacity ratio (80%-98%) of the silicon-carbon composite material. The higher the capacity and the first efficiency, the more conducive to the improvement of the energy density of the secondary battery in practical applications. The technical problems of insufficient energy density, cycle and rate of the silicon-carbon composite negative electrode material formed by silicon and carbon in the prior art are solved. The composite negative electrode material can be used alone or in combination with graphite, hard carbon, other silicon-based materials, and carbon-based materials.

[0021] In some embodiments, the composite negative electrode material obtained after silicon is deposited on the negative electrode material precursor, the mass proportion of silicon element is in the range of 10%-60%. The increase in the mass content of silicon element is conducive to the improvement of gram capacity and first efficiency, which is conducive to improving the energy density of the secondary battery, but when the silicon element content is too high, there is a risk of a decrease in the cycle performance and rate performance of the secondary battery. When the silicon element content is too low, although it is conducive to the improvement of the cycle and rate performance of the secondary battery, it is not conducive to the improvement of gram capacity and first efficiency, and the improvement of the energy density of the secondary battery. The proportion of carbon element is in the range of 30%-80%, and the reduction of the mass content of carbon element is conducive to the improvement of gram capacity and first efficiency, which is conducive to improving the energy density of the secondary battery, but when the carbon element content is too low, there is a risk of a decrease in the cycle performance and rate performance of the secondary battery. When the carbon element content is too high, although it is conducive to the improvement of the cycle and rate performance of the secondary battery, it is not conducive to the improvement of gram capacity and first efficiency, and the improvement of the energy density of the secondary battery. Therefore, in order to improve the performance of the secondary battery, the mass proportion of silicon element in the composite negative electrode material needs to be controlled within the scope of the present invention. The preferred range of oxygen content is 0.01%-10%. Too low oxygen content is not conducive to the stabilization treatment of active nano-silicon, and too high oxygen content reduces the gram capacity and initial efficiency of the composite negative electrode material, which is not conducive to the improvement of battery energy density.

[0022] A second aspect of the present invention provides a method for preparing a negative electrode material precursor, which comprises the following steps: The preparation method of the negative electrode material precursor includes a gas activation method and an alkali activation method, and the gas activation method includes at least one of the following steps: (the flow rates of the inert gas and the activation gas are determined according to the weight of the carbon source precursor in the reaction chamber) G1, carbonization step, pyrolysis and carbonization of the carbon precursor, introducing inert gas into the reaction chamber of the reactor 1 containing the carbon source precursor, the inert gas flow rate is 0.2-5L / min / kg, and the reaction chamber is heated to TG1, the TG1 range is 400-1500℃, and carbonization and cracking reaction is carried out, and TG1 is kept warm for 0-24h. During this process, the surface pressure 1 of the reaction chamber is 0.5kpa-50kpa; after the cracking reaction, a porous carbon carrier intermediate is obtained; G2, activation step, the negative electrode material precursor intermediate is transferred to the reaction chamber of reactor 2, inert gas is passed and the temperature is raised to TG2, the inert gas flow rate is 0.2-5L / min / kg, and the TG2 range is 500-1100°C, and then the activation gas containing CO2 is passed into the reaction chamber, the activation gas flow rate is 0.2-5L / min / kg, and the activation reaction is carried out, and the TG2 is kept warm for 0.1-80h. During this process, the surface pressure 2 of the reaction chamber is 0.5kpa-50kpa; after the activation reaction, the negative electrode material precursor is obtained.

[0023] Or G2', activation step, the negative electrode material precursor intermediate is transferred to the reaction chamber of the reactor 2', the inert gas is passed and the temperature is raised to TG2', the inert gas flow rate is 0.2-5L / min / kg, the TG2' range is 200-1300℃, and then the activation gas containing H2O is passed into the reaction chamber, the activation gas flow rate is 0.2-5L / min / kg, the activation reaction is carried out, and the TG2 is kept warm for 0.1-50h. During this process, the surface pressure 2' of the reaction chamber is 0.5kpa-50kpa; after the activation reaction, a porous carbon carrier is obtained.

[0024] In some embodiments, the carbon source precursor of the G1 process comprises at least one of a phenolic resin or other high molecular polymer (e.g., polyacrylonitrile, melamine resin, epoxy resin, urea-formaldehyde resin, polyester resin, polyamide resin, polyimide resin, polycarbonate, acrylonitrile copolymer), a biomass carbon source (e.g., coconut shell, fruit shell, fruit core, tea shell, wood, cellulose, straw, bamboo, walnut shell, sugar, starch, glucose) and a fossil raw material carbon source (e.g., asphalt, coal, petroleum); In some embodiments, the phenolic resin is a resin formed by polycondensation of phenolic compounds and aldehyde compounds under the action of a catalyst, wherein the phenolic compound comprises at least one of phenol, resorcinols, cresols, mixed cresols, nonylphenol, octylphenol, xylenol, cardanol, aralkylphenol, bisphenol A, etc., and the aldehyde compound comprises at least one of formaldehyde, paraformaldehyde, furfural, acetaldehyde, etc. The catalyst comprises an acid, a base, and a salt. The acid comprises other acids such as hydrochloric acid, oxalic acid, phosphoric acid, and sulfuric acid, the base comprises ammonia water, sodium hydroxide, barium hydroxide, magnesium oxide, aniline, HMT, etc., and the salt comprises sodium carbonate, potassium carbonate, etc.

[0025] In some embodiments, the phenolic resin element composition contains C, O, and H. In order to improve the strength of the negative electrode material precursor, a high cross-linked, high residual carbon (>40%), high molecular weight (>700) phenolic resin or a modified phenolic resin is preferred.

[0026] In some embodiments, the phenolic resin comprises phenol formaldehyde resin, which has obvious advantages in cost and strength.

[0027] In some embodiments, the G2 step is used for gas activation to obtain a negative electrode material precursor with a good pore structure; In some embodiments, the G2' step is used for gas activation, which has a simple process, low cost, high cost performance, and is easy to scale up; In some embodiments, the activation step comprises two activation steps, G2 and G2', to achieve a high-efficiency activation effect; In some embodiments, the inert gas is at least one of nitrogen, argon, and helium, used as a protective gas. The inert gas flow rate ranges from 0.25 to 4.5 L / min / kg. If the flow rate is too large, the reactants are at risk of being blown away, resulting in a reduced yield; if the flow rate is too small, it is difficult to form a good protective atmosphere, which is not conducive to the stability or safety of the carbonization process.

[0028] In some embodiments, the activation gas is at least one of CO2, H2O, O2, flue gas, and air. In the process of G2 or G2', the activation gas flow rate range is 0.2-5L / min / kg. If the flow rate is too large, the reactants may be blown away and there may be a risk of over-activation. If the flow rate is too small, there may be a risk of substandard activation. This is not conducive to obtaining porous carbon with a good pore structure. In some embodiments, TG1 is in the range of 500-1200° C. A too low temperature may result in insufficient carbonization, while a too high temperature may be beneficial to the ordered transformation of amorphous carbon but may be detrimental to the subsequent activation effect. In some embodiments, the TG1 holding time is 0.2-12h. If the holding time is too short, there is a risk of insufficient carbonization. If the holding time is too long, although it is beneficial to the ordered transformation of amorphous carbon, it is not conducive to the subsequent activation effect. In some embodiments, TG2 is in the range of 700-1000° C. Too low a temperature may result in insufficient activation, while too high a temperature may result in overactivation, and the yield may be reduced. In some embodiments, the TG2 holding time is 1-50h. If the holding time is too short, there is a risk of insufficient activation and failure to obtain a suitable pore volume and pore size. If the holding time is too long, there is a risk of over-activation, which not only results in high energy consumption but also reduces the yield, and is not conducive to obtaining a negative electrode material precursor with uniform pore size and high pressure resistance, which is not conducive to the cycle stability of the secondary battery. In some embodiments, TG2' is in the range of 500-1000° C. A too low temperature may result in insufficient activation, while a too high temperature may result in overactivation, which may reduce the yield and be detrimental to obtaining a negative electrode material precursor with high compressive strength. In some embodiments, the TG2' holding time is 1-40h. If the holding time is too short, there is a risk of insufficient activation and failure to obtain a suitable pore volume and pore size. If the holding time is too long, there is a risk of over-activation, which not only results in high energy consumption, but also reduces the yield and is not conducive to obtaining a negative electrode material precursor with uniform pore size and high pressure resistance, which is not conducive to the cycle stability of the secondary battery. In some embodiments, in the G1 process, the gauge pressure 1 is 0.5 kPa to 25 kPa, in the G2 process, the gauge pressure 2 is 0.5 kPa to 25 kPa, and in the G2' process, the gauge pressure 2' is 0.5 kPa to 25 kPa. When the gauge pressure is too low, it is not conducive to forming a good protective atmosphere, and there is a risk of air entering, which is not conducive to safe production; in the G2 and G2' processes, the activated gas is not easy to enter the interior of the negative electrode material precursor intermediate, which is not conducive to forming a negative electrode material precursor with uniform pore size. When the gauge pressure is too high, it approaches or exceeds the pressure resistance limit of some equipment accessories, which is not conducive to safe production.

[0029] In some embodiments, the heat treatment device for pyrolysis carbonization and activation treatment can be any reaction device with a heating mechanism, without any particular limitation, and may include a heating device for treatment using a continuous method, an intermittent method, etc. Specifically, at least one of a fluidized bed reactor, a vibrating bed rotary kiln, a vertical moving bed reactor, a tunnel furnace, an intermittent furnace, a push plate kiln, a roller kiln, a box furnace, and a tube furnace may be appropriately selected according to the purpose; The preparation method of the negative electrode material precursor includes a gas activation method and an alkali activation method. The alkali activation method includes the following steps: (the flow rates of the inert gas and the oxygen-containing gas are determined according to the weight of the carbon source precursor in the reaction chamber) K1, carbonization step, inert gas is introduced into the reaction chamber of the reactor 3 containing the carbon source precursor, the inert gas flow rate is 0.2-5L / min / kg, and the reaction chamber is heated to TK1, TK1 range is 400-1500℃, carbonization and cracking reaction is carried out, TK1 is kept warm for 0-24h. During this process, the surface pressure 1 of the reaction chamber is 0.5kpa-50kpa; K2, activation step, after the carbon source precursor carbonized material and the alkaline activator are fully mixed in a certain proportion, they are transferred to the reaction chamber of the reactor 4, inert gas is introduced and the temperature is raised to TK2, the inert gas flow rate is 0.2-5L / min / kg, the TK2 range is 400-1000℃, the activation reaction is carried out, and the TK2 is kept warm for 0.01-12h. During this process, the surface pressure 2 of the reaction chamber is 0.5kpa-50kpa; after the activation reaction, the negative electrode material precursor intermediate 1 is obtained; K3, passivation step, introducing oxygen-containing gas into the reaction chamber of reactor 4 for passivation treatment, the oxygen-containing gas flow rate is 0.2-5L / min / kg, and the product after passivation treatment is negative electrode material precursor intermediate 2; during this process, the surface pressure 2 of the reaction chamber is 0.5kpa-50kpa; The negative electrode material precursor intermediate 2 is pickled, washed with water, and dried to remove excess metal impurities and excess water to obtain a negative electrode material precursor. The metal impurity element content in the negative electrode material precursor is less than 100 ppm, and the water content is less than 20 mg / g.

[0030] In some embodiments, the inert gas contains at least one of nitrogen, argon, and helium, which is used as a protective gas.

[0031] In some embodiments, in the K1 process and the K2 process, the inert gas flow rate range is 0.25-4.5 L / min / kg; in the K1 process, if the flow rate is too large, the reactants are at risk of being blown away, resulting in a reduced yield; if the flow rate is too small, it is difficult to form a good protective atmosphere, which is not conducive to the stability or safety of the carbonization process.

[0032] In the K2 process, if the flow rate is too large, the reactants are at risk of being blown away, resulting in a lower yield; if the flow rate is too small, it is difficult to form a good protective atmosphere because the intermediate by-products such as K vapor and H2 are highly active, which is not conducive to the stability or safety of the activation process.

[0033] In some embodiments, TK1 is in the range of 500-850° C. A too low temperature may result in insufficient carbonization, while a too high temperature may result in better pyrolysis and be beneficial to the ordered transformation of amorphous carbon, but may be detrimental to the subsequent activation effect. In some embodiments, the TK1 holding time is 0.1-12h. If the holding time is too short, there is a risk of insufficient carbonization. If the holding time is too long, although it is beneficial to the ordered transformation of amorphous carbon, it is not conducive to the subsequent activation effect. In some embodiments, TK2 is in the range of 500-850° C. Too low a temperature may result in insufficient activation, while too high a temperature may result in overactivation, which may reduce the yield and may lead to the appearance of potassium vapor, which may be detrimental to the stability or safety of the activation process. In some embodiments, the TK2 holding time is 0.1-10h. If the holding time is too short, there is a risk of insufficient activation and failure to obtain a suitable pore volume and pore size. If the holding time is too long, there is a risk of over-activation, which not only results in high energy consumption but also reduces the yield, and is not conducive to obtaining a negative electrode material precursor with uniform pore size and high pressure resistance, which is not conducive to the cycle stability of the secondary battery. In some embodiments, in the K2 process, the alkaline activator contains KOH. The molar ratio of the carbon source precursor carbonized material to the alkaline activator is in the range of 2-0.2. If the molar ratio is too low, there is a risk of failing to achieve the activation effect, failing to obtain a high pore volume, and after depositing the silicon-containing material, it is not conducive to obtaining a composite negative electrode material with a high gram capacity and first efficiency, which is not conducive to improving the energy density of the secondary battery; if the molar ratio is too high, there is a risk of over-activation, resulting in a reduced yield and increased cost, which is not conducive to forming a negative electrode material precursor with a uniform pore structure, and thus is not conducive to obtaining a composite negative electrode material with good cycle performance.

[0034] In some embodiments, in the K3 process, the oxygen-containing gas contains at least one of CO2, H2O, and O2. In the K3 process, the highly active components containing K element or hydrogen in the passivation process 2 are unstable when exposed to air, which is conducive to safe discharge and safe production.

[0035] In some embodiments, K1 process, the gauge pressure 1 is 0.5kPa to 25kPa, K2 process, the gauge pressure 2 is 0.5kPa to 25kPa, In the K3 process, the gauge pressure 3 is 0.5 kPa to 25 kPa. When the gauge pressure is too low, it is not conducive to forming a good protective atmosphere, and there is a risk of air entering, which is not conducive to safe production. When the gauge pressure is too high, it approaches or exceeds the pressure limit of some equipment accessories, which is not conducive to safe production.

[0036] In some embodiments, the heat treatment apparatus for pyrolysis carbonization and activation and passivation treatment can be any reaction apparatus having a heating mechanism, and is not particularly limited. Examples include heating apparatuses that perform treatment using a continuous method, a batch method, and the like.

[0037] Specifically, at least one of a fluidized bed reactor, a vibrating bed rotary kiln, a vertical moving bed reactor, a tunnel furnace, a batch furnace, a pusher kiln, a roller kiln, a box furnace and a tube furnace can be appropriately selected according to its purpose; In some embodiments, regarding the negative electrode material precursor used for the pyrolytic deposition of silicon, the particle size control method includes the following steps: taking the carbonized or activated carbon-containing material, preferably pulverizing and classifying it in advance.

[0038] Specifically, it is preferred to perform a primary pulverization and classification of large particles of carbon-containing materials to a size that can be put into a micro-pulverizer, and then perform a secondary pulverization on them by a micro-pulverizer. The particle size of the carbon-containing material obtained by the secondary pulverization reaches the particle size of the silicon-carbon composite negative electrode material. The manufacture of the particle size of the above-mentioned negative electrode material precursor also includes at least one step of pulverization and classification of the carbon-containing material, or no pulverization or classification is performed, and the particle size of the silicon-carbon composite negative electrode material is directly reached after carbonization activation.

[0039] In some embodiments, the heat-treated product obtained by the above heat treatment has a plurality of particles bonded together, so it can be crushed and classified according to the preferred particle size range. Crushing and classification equipment includes common jaw crushers, air flow mills, mechanical mills, air flow classifiers, etc.

[0040] In some embodiments, the above-mentioned pulverizing equipment includes conventional pulverizing equipment such as a roller mill and a mechanical crusher for preliminary pulverization, and ultrafine air flow crushing equipment, such as a collision-type air flow pulverizer, a flat air flow pulverizer, a fluidized bed air flow pulverizer, an impact ring air flow pulverizer, etc. The grading equipment includes grading without a net, grading with a net is screening, and grading without a net is fluid mechanics grading. Fluids include gases such as air, and liquids such as water.

[0041] The method for preparing the silicon-carbon composite negative electrode material using this negative electrode material precursor is specifically to attach a silicon-containing material to the porous carbon negative electrode material precursor, and then perform a coating treatment or passivation treatment on the carbon-containing material; the method of attaching the silicon-containing material or the carbon-containing material is to introduce a silicon source gas or a carbon source gas into the reaction chamber containing the negative electrode material precursor for pyrolysis deposition, and by controlling the flow rate, concentration, pressure, temperature and reaction time of the silicon source gas or the carbon source gas, the silicon-containing material and the carbon skeleton are evenly distributed, and effective surface coating is achieved. This method is environmentally friendly, simple in process, and is conducive to the large-scale production of high-performance composite negative electrode materials. The silicon source gas contains monosilane, ethyl At least one of silane, silicon vapor, trichlorosilane and dichlorosilane; the silicon source gas or carbon source gas further comprises a diluent gas, the diluent gas comprises at least one of hydrogen, argon and nitrogen; the carbon source gas comprises but is not limited to a hydrocarbon gas introduced for carbon deposition treatment; wherein the hydrocarbon gas comprises but is not limited to at least one of methane, ethane, propane, ethylene, propylene and acetylene; the passivation treatment method comprises but is not limited to introducing an oxygen-containing gas into an intermediate reaction chamber containing deposited silicon for passivation treatment; the oxygen-containing gas comprises but is not limited to at least one of air, oxygen, carbon dioxide, water vapor, methanol vapor and ethanol vapor; The oxygen-containing gas also includes a mixture of the above-mentioned gas and an inert gas, wherein the inert gas includes but is not limited to at least one of hydrogen, argon and nitrogen; the passivation treatment method also includes mixing the powder material after cracking the silicon source with an oxygen-containing liquid for passivation treatment. The liquid includes but is not limited to one or more of electrolyte solvents, additives, H2O2, H2O, potassium permanganate oxygen-containing substances; After the passivation treatment, the oxygen content of the material increases, the storage stability and the processing stability increase, and the passivation treatment also helps to improve the chemical and electrochemical stability of the material.

[0042] The third aspect of the present invention provides a secondary battery electrochemical device, comprising a negative electrode, a positive electrode, an electrolyte and a separator. The negative electrode comprises a negative electrode material layer, the negative electrode material layer comprises a negative electrode active material, the negative electrode active material comprises a composite negative electrode material, and the composite negative electrode material comprises the negative electrode material precursor of the first aspect or the composite negative electrode material precursor prepared by the preparation method of the second aspect.

[0043] In some embodiments, the secondary battery electrochemical device of the present invention is a high energy density fast-charge lithium ion battery, which comprises a negative electrode, a positive electrode, an electrolyte and a separator.

[0044] The negative electrode for the lithium ion secondary battery of the present invention can be obtained in the following manner: the negative electrode active material for the lithium ion secondary battery, a binder, a solvent or a solvent such as water, and a thickener, a conductive agent, etc. as required are mixed to prepare a coating liquid (slurry), the coating liquid is imparted (coated) on the collector, the solvent or water is dried, and pressure molding is performed to form a negative electrode material layer.

[0045] In some embodiments, the electrochemical device of the present invention is a lithium ion battery, the negative electrode of the lithium ion battery includes a negative electrode current collector and a negative electrode material layer coated on the negative electrode current collector, the negative electrode material layer includes a negative electrode active material, and the positive electrode of the lithium ion battery includes a positive electrode current collector and a positive electrode material layer coated on the positive electrode current collector, the positive electrode material layer includes a positive electrode active material.

[0046] The method of coating the coating liquid on the current collector is not particularly limited, including metal mask printing, electrostatic coating, dip coating, spraying, roller coating, doctor blade, gravure coating, screen printing and other known methods. The electrode coating thickness is preferably 30um to 200um, and the electrode coating weight is preferably 1mg / cm 2 ~50mg / cm 2 The higher the electrode coating thickness and weight, the higher the volume energy density of the negative electrode. After coating, the solvent or water is removed by heating and drying, and then cold pressing is performed by a flat press, calendering roller, etc. as needed.

[0047] In some embodiments, the negative electrode active material is a mixed active material of a composite negative electrode material using the negative electrode material precursor of the present invention and an existing negative electrode active material; the mass content of the composite negative electrode material is 0.1% to 100% of the mass of the negative electrode active material.

[0048] In some embodiments, the mass content of the composite negative electrode material using the negative electrode material precursor of the present invention is in the range of any two of 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100%.

[0049] In some embodiments, the existing negative electrode active material includes at least one of a carbon material and a non-carbon material, and the carbon material includes at least one of mesophase microcarbon beads, natural graphite, artificial graphite, hard carbon, and soft carbon.

[0050] The non-carbon material includes at least one of silicon, silicon oxygen, metal-doped silicon oxygen, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel-structured lithiated TiO2-Li4Ti5O12 or Li-Al alloy.

[0051] In some embodiments, the negative electrode material layer further comprises a conductive agent and a binder. The mass content of the conductive agent in the negative electrode material layer is preferably 0.01% to 10%.

[0052] When the content of the conductive agent is greater than or equal to 0.01%, the negative electrode material layer has good electrical contact and can suppress the risk of contact resistance damage due to expansion and contraction during charging and discharging. When the content of the conductive agent is less than or equal to 10%, the risk of reduced energy density can be suppressed.

[0053] The mass content of the binder in the negative electrode material layer is preferably 0.1% to 10%.

[0054] The content of the binder is greater than or equal to 0.1%, the negative electrode material layer is well bonded, and the risk of the negative electrode being damaged due to expansion and contraction during charging and discharging can be suppressed. The content of the binder is less than or equal to 10%, which can suppress the risk of increasing electrode resistance.

[0055] In some embodiments, the negative electrode conductive agent includes, but is not limited to, at least one of a carbon-based material, a metal-based material, a conductive polymer, an oxide with conductivity, a nitride with conductivity, and the like. In some embodiments, the carbon-based material includes at least one of conductive carbon black, carbon nanotubes, acetylene black, graphene, carbon fiber, flake graphite, Ketjen black, natural graphite, and artificial graphite. The carbon nanotube may include, but is not limited to, at least one of a single-walled carbon nanotube and a multi-walled carbon nanotube. In some embodiments, the metal-based material includes at least one of copper, nickel, aluminum, or silver.

[0056] In some embodiments, the conductive polymer is at least one of polyaniline, polythiophene, polyacetylene, polypyrrole, and polyphenylene derivatives.

[0057] In some embodiments, the negative electrode binder includes, but is not limited to, at least one of copolymer-based materials and polymer-based materials; the copolymer-based binder includes at least one of styrene-butadiene copolymers, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, (meth)acrylonitrile and other ethylenically unsaturated carboxylic acids and (meth)acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid and other ethylenically unsaturated carboxylic acids copolymerized (meth)acrylic acid copolymers; some groups of the copolymer are substituted by one or more of Na, K, and Li.

[0058] The polymer compound-based binder includes at least one of polyurethane, polyacrylonitrile, polyimide, polyamide-imide, polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, and polyphosphazene; In some embodiments, the binder and a thickener for adjusting the viscosity can be used together. The mass content of the thickener in the negative electrode material layer is preferably 0.1% to 10%, more preferably 0.2% to 8%. The thickener includes at least one of carboxymethyl cellulose (sodium), hydroxymethyl cellulose, methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid (ester), oxidized starch, phosphorus oxidized starch, casein, etc.; In some embodiments, for ease of manufacturing, a negative electrode binder slurry may be prepared first. The negative electrode binder slurry includes a mixture of solvent or water and one or more of the negative electrode binders mentioned above. In addition, it also includes a mixture of one or more of the negative electrode binders mentioned above and one or more of the conductive agents.

[0059] In some embodiments, the negative electrode further includes a negative electrode current collector, which includes at least one of copper foil, copper foil coated with a conductive agent, copper alloy foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, and a polymer substrate coated with a conductive metal. The thickness of the negative electrode current collector is not particularly limited, for example, the thickness is 4 μm to 25 μm.

[0060] In the present application, the negative electrode material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode current collector. The "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application is not particularly limited as long as the purpose of this application can be achieved. As materials for the current collector, for example, aluminum, copper, nickel, titanium, stainless steel, porous metal (foamed metal) and carbon paper can be listed. There is no particular limitation on the shape of the above-mentioned current collector, for example, foil, perforated foil and mesh can be listed.

[0061] In some embodiments, in the negative electrode material layer of the negative electrode formed after the pressurization, the density of the negative electrode active material is 0.6 g / cc to 1.9 g / cc.

[0062] In some embodiments, the positive electrode active material can be any compound that can be doped or inserted with lithium ions, including but not limited to at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese aluminum oxide, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, and spinel lithium nickel manganese oxide.

[0063] The positive electrode active material includes a ternary material Li Nia Cob MncO2 or LiNid Coe Al fO2, wherein a+b+c≤1, 0<a<1, 0<b<1, 0<c<1; d+e+f≤1, wherein 0<d<1, 0<e<1, 0<f<1. In some embodiments, The positive electrode active material includes at least one of LiNi1 / 3Co1 / 3Mn1 / 3O2, LiNi0.5Co0.2Mn0.3O2, LiNi0.8Co0.1Mn0.1O2, LiNi0.6Co0.2Mn0.2O2, LiNi0.8Co0.15Al0.05O2 or LiNi0.88Co0.11Mn0.11O2.

[0064] The particle size Dv99:Dv50 ratio of the positive electrode active material is in the range of 2.2 to 2.8.

[0065] In some embodiments, the positive electrode material layer further comprises a conductive agent and a binder. The mass content of the conductive agent in the positive electrode material layer is preferably 0.01% to 10%. The mass content of the binder in the positive electrode material layer is preferably 0.1% to 10%.

[0066] In some embodiments, the positive electrode conductive agent includes, but is not limited to, at least one of a carbon-based material, a metal-based material, a conductive polymer, an oxide with conductivity, a nitride with conductivity, and the like.

[0067] In some embodiments, the carbon-based material includes at least one of conductive carbon black, carbon nanotubes, acetylene black, graphene, carbon fiber, flake graphite, Ketjen black, natural graphite, and artificial graphite.

[0068] The carbon nanotubes may include but are not limited to at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes. In some embodiments, the metal-based material includes at least one of copper, nickel, aluminum or silver.

[0069] In some embodiments, the conductive polymer is at least one of polyaniline, polythiophene, polyacetylene, polypyrrole, and polyphenylene derivatives.

[0070] In some embodiments, the positive electrode binder includes, but is not limited to, at least one of polyvinylidene fluoride, modified polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified SBR rubber or polyurethane.

[0071] In some embodiments, the positive electrode further includes a positive electrode current collector, which includes at least one of aluminum foil, aluminum foil coated with a conductive agent, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, and a polymer substrate coated with a conductive metal.

[0072] In some embodiments, the positive electrode can be obtained by forming a positive electrode material layer on the surface of the positive electrode current collector in the same way as the negative electrode. The current collector in the positive electrode can use the same current collector as described in the negative electrode above.

[0073] In some embodiments, the positive electrode manufacturing method is to mix the above-mentioned positive electrode active material, organic binder such as polyvinylidene fluoride, solvent such as N-methyl-2-pyrrolidone, γ-butyrolactone, and conductive agent to prepare a positive electrode coating liquid, apply the positive electrode coating liquid on at least one side of a current collector such as aluminum foil, then heat to remove the solvent, and then perform cold pressing as needed.

[0074] The secondary battery provided by the present invention further comprises an electrolyte. The electrolyte is at least one of a solid electrolyte, a gel electrolyte, and an electrolyte, and the electrolyte comprises a lithium salt, a non-aqueous solvent, and an additive. The electrolyte of the present invention may be an electrolyte known in the prior art.

[0075] In some embodiments, the lithium salt includes one or more of inorganic lithium salts LiClO4, LiPF6, LiAsF6, LiBF4, LiAlCl4, LiSCN, and organic lithium salts LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, lithium bis(difluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), organic borate lithium salts, lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), and organic lithium phosphate salts.

[0076] The above lithium salts can be used alone or in combination of two or more. The concentration of the lithium salt in the electrolyte is 0.5 mol / L to 2 mol / L.

[0077] In some embodiments, the non-aqueous solvent may be at least one of a carbonate compound, a carboxylate compound, an ether compound, and other organic solvents.

[0078] The carbonate compound may be at least one of a cyclic carbonate compound, a chain carbonate compound, and a fluorinated carbonate compound. Examples of cyclic carbonate compounds are at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and vinylene carbonate (VC). Chain carbonate compounds are at least one of diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), dimethyl carbonate (DMC), and dipropyl carbonate (DPC).

[0079] The fluorinated carbonate compound is at least one of fluoroethylene carbonate (FEC), 1,1-difluoroethylene carbonate, 1,2-difluoroethylene carbonate (DFEC), 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, and trifluoromethylethylene carbonate.

[0080] The carboxylate compound is at least one of methyl formate (MF), methyl acetate (MA), ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate (EP), propyl propionate, methyl butyrate (MB), γ-butyrolactone, decanoic acid lactone, valerolactone, mevalonolactone, and caprolactone.

[0081] The ether compound is at least one of tetrahydrofuran (THF), 2-methyltetrahydrofuran (2Me-THF), 1,3-dioxolane (DOL), dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, ethoxymethoxyethane, dibutyl ether, tetraethylene glycol dimethyl ether, and diethylene glycol dimethyl ether (DG).

[0082] The other non-aqueous solvents are sulfur-containing solvents such as ethyl methyl sulfone (EMS), dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, ethylene sulfite (ES), propylene sulfite (PS), diethyl sulfite (DES), dimethyl sulfite (DMS), and nitrogen-containing solvents such as 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, and P-containing solvents such as trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate ester.

[0083] In some embodiments, the solvent used in the electrolyte of the present application includes one or more of the above.

[0084] In some embodiments, the additive accounts for 0.02%-30% of the electrolyte mass.

[0085] The above-mentioned non-aqueous solvent and lithium salt can be used as additives.

[0086] The additives of the present invention may be additives known in the prior art.

[0087] In some embodiments, the electrolyte additive includes, but is not limited to, one or more of a compound having 2-3 cyano groups, a cyclic carbonate containing a carbon-carbon double bond, a compound containing a sulfur-oxygen double bond, and lithium difluorophosphate.

[0088] The secondary battery provided by the present invention further comprises a separator, which is located between the positive electrode and the negative electrode to prevent short circuit. The separator may comprise at least one of a substrate layer and a coating treatment layer.

[0089] In some embodiments, the material of the substrate layer is at least one of polyethylene, polypropylene, polyethylene terephthalate, polyimide, polyphenylene sulfide (PPS), and cellulose, and the substrate layer is a non-woven fabric, film or composite film with a porous structure, including at least one of a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric, and a polypropylene-polyethylene-polypropylene porous composite film.

[0090] In some embodiments, at least one surface of the substrate layer has a coating treatment layer, and the coating treatment layer is at least one of a polymer layer and an inorganic layer. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are at least one of oxides (e.g., aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, zirconium oxide, magnesium oxide, titanium oxide), nitrides (e.g., boron nitride, silicon nitride, aluminum nitride), silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, styrene-butadiene rubber, polyamide, polyacrylonitrile, polyacrylic acid, polyvinylpyrrolidone, polyethylene alkoxy, polytetrafluoroethylene and polyhexafluoropropylene.

[0091] The polyacrylic acid may be polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate, polymethyl methacrylate, polyacrylate, polyacrylic acid, or polyacrylate.

[0092] The polymer layer contains a polymer, and the material of the polymer is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, polyoxyethylene polyoxypropylene block copolymer, siloxane, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate and polyvinylpyrrolidone.

[0093] The electrochemical device in which the composite negative electrode material using the negative electrode material precursor of the present invention can be used is not particularly limited, and can include any device in which an electrochemical reaction occurs.

[0094] In some embodiments, the electrochemical device includes, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery, a solid-state battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery, and the like.

[0095] The electrochemical device manufacturing method of the present invention includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a packaging bag, injecting an electrolyte into the packaging bag and sealing it to obtain an electrochemical device; or stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a packaging bag, injecting an electrolyte into the packaging bag and sealing it to obtain an electrochemical device; Alternatively, the positive electrode sheet, the separator and the negative electrode sheet are stacked in order and wound, the spirally wound assembly is inserted into the battery can, the tabs welded to the negative electrode current collector are welded to the bottom of the battery can, and then the electrolyte is injected into the battery can, and then the tabs welded to the positive electrode current collector are welded to the battery cover, an insulating gasket is added, and then the cover and the battery can are welded and sealed to obtain a battery. In addition, overcurrent protection components, guide plates, etc. can also be placed in the packaging bag as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.

[0096] The form of the lithium ion secondary battery of the present invention is not particularly limited, and examples thereof include wound batteries, thin film batteries, button batteries, coin batteries, laminated batteries, cylindrical batteries, and prismatic batteries.

[0097] The fourth aspect of the present invention provides an electronic device, which includes the secondary battery electrochemical device of the third aspect. The electronic device of the present invention is not particularly limited and can be used for any purpose known in the prior art. In some embodiments, the electronic devices of the present invention include, but are not limited to, automobiles, motorcycles, laptop computers, portable phones, headphones, cameras, video recorders, LCD televisions, portable cleaners, household batteries, power tools, backup power supplies, motors, lighting fixtures, toys, game consoles, clocks, etc.

[0098] Compared with the prior art, the present invention has at least the following beneficial effects: The present application provides a negative electrode material precursor, a negative electrode material, a secondary battery and an electronic device. The secondary battery includes a negative electrode plate, and the negative electrode plate includes a composite negative electrode material using the negative electrode material precursor of the present invention. The negative electrode material precursor provided by the present invention contains low-crystalline carbon, and the carbon Raman peak Id / Ig ratio is 0.7 to 1.7; the mass proportion of silicon element in the negative electrode material precursor is in the range of 0.001%≤X≤5%, the proportion of carbon element is in the range of 70%≤Y<100%, and the proportion of oxygen element is 0.1%-10%; The negative electrode material precursor of the present invention has a Dv50 of 3 μm to 15 μm, a Dv99 of 6 μm to 30 μm, and Dn10 and Dv10 satisfy the following relationship: 0.1≤Dn10 / Dv10≤0.9; the sphericity of the negative electrode material precursor particles is preferably 50%-97%, and the negative electrode material precursor has a low closed pore area ratio, >100 nm closed pore area ratio <20%; the negative electrode material precursor has a high BET 1000-4000 and a high GM value (12-32); due to these excellent structural characteristics, the silicon-carbon composite negative electrode material prepared by the negative electrode material precursor of the present invention can alleviate the expansion and contraction caused by the insertion and extraction of lithium ions, and at the same time can reduce the capacity reduction caused by the SEI repair of the surface of the silicon-carbon composite per unit volume, so the composite negative electrode material has a high first efficiency of 80-96%, a high theoretical capacity (600-2500 mAh / g), greatly improving the battery's energy density, expansion, cycle stability, and rate performance.

[0099] The composite negative electrode material prepared from the negative electrode material precursor provided by the present invention greatly improves the capacity and energy density of the secondary battery, and at the same time, significantly improves the expansion, cycle performance and rate performance of the secondary battery.

[0100] Of course, any product or method of the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0101] Figure 1 The particle size volume distribution of the negative electrode material precursor provided by the present invention Figure 1 ;

[0102] Figure 2 The particle size distribution of the negative electrode material precursor provided by the present invention Figure 1 ;

[0103] Figure 3 The particle size volume distribution of the negative electrode material precursor provided by the present invention Figure 2 ;

[0104] Figure 4 The particle size distribution of the negative electrode material precursor provided by the present invention Figure 2 ; Figure 5 The particle size volume distribution of the negative electrode material precursor provided by the present invention Figure 3 ; Figure 6 The particle size distribution of the negative electrode material precursor provided by the present invention Figure 3 ; Figure 7 The particle size volume distribution of the negative electrode material precursor provided by the present invention Figure 4 ; Figure 8The particle size distribution of the negative electrode material precursor provided by the present invention Figure 4 ; Fig. 9 The particle size volume distribution of the negative electrode material precursor provided by the present invention Figure 5 ; Fig.10 The particle size distribution of the negative electrode material precursor provided by the present invention Figure 5 ; Fig.11 The particle size volume distribution of the negative electrode material precursor provided by the present invention Figure 6 ; Fig.12 The particle size distribution of the negative electrode material precursor provided by the present invention Figure 6 ; Fig.13 Raman spectrum of the negative electrode material precursor provided by the present invention Figure 1 ; Fig.14 Raman spectrum of the negative electrode material precursor provided by the present invention Figure 2 Fig.15 Raman spectrum of the negative electrode material precursor provided by the present invention Figure 3 . Fig.16 XRD of the negative electrode material precursor provided by the present invention Figure 1 ; Fig.17 XRD of the negative electrode material precursor provided by the present invention Figure 2 ; Fig.18 XRD of the negative electrode material precursor provided by the present invention Figure 3 ; Fig.19 XRD of the negative electrode material precursor provided by the present invention Figure 4 ; Fig. 20 The SEM-CP of the negative electrode material precursor provided by the present invention is Figure 1 ; Fig.21 Schematic diagram of the sphericity of the negative electrode material precursor provided by the present invention Figure 1 ; Fig. 22 The SEM-CP of the negative electrode material precursor provided by the present invention is Figure 2 ; Fig.23 The Ar gas adsorption-desorption isotherm provided by the present invention is Figure 1 ; Fig.24 The pore size-pore volume increment distribution provided by the present invention Figure 1 ; Fig.25The Ar gas adsorption-desorption isotherm provided by the present invention is Figure 2 ; Fig.26 The pore size-pore volume increment distribution provided by the present invention Figure 2 ; Fig. 27 The Ar gas adsorption-desorption isotherm provided by the present invention is Figure 2 ; Fig.28 The pore size-pore volume increment distribution provided by the present invention Figure 2 ; Fig.29 The Ar gas adsorption-desorption isotherm provided by the present invention is Figure 3 ; Fig.30 The pore size-pore volume increment distribution provided by the present invention Figure 3 ; Fig.31 TG curve and weight loss data changes of the negative electrode material precursor provided by the present invention Figure 1 ; Fig.32 TG curve and weight loss data changes of the negative electrode material precursor provided by the present invention Figure 2 ; Fig.33 TG curve and weight loss data changes of the negative electrode material precursor provided by the present invention Figure 3 ; Fig.34 TG curve and weight loss data changes of the negative electrode material precursor provided by the present invention Figure 4 ; Fig.35 TG curve and weight loss data changes of the negative electrode material precursor provided by the present invention Figure 5 ; Fig.36 A schematic diagram of the minimum circumscribed circle of the negative electrode material precursor provided by the present invention; Fig.37 The SEM-CP and single closed pore ratio calculation method provided by the present invention; Fig.38 It is a schematic diagram of the minimum circumscribed ellipse of the present invention; Fig.39 The SEM-CP and single particle sphericity calculation method provided by the present invention; Fig.40 The capacity-voltage curve of the composite negative electrode material provided by the present invention Figure 1 ; Fig.41 DQ / DV curve of the composite negative electrode material provided by the present invention Figure 1 ; Fig.42The capacity-voltage curve of the composite negative electrode material provided by the present invention Figure 2 ; Fig.43 DQ / DV curve of the composite negative electrode material provided by the present invention Figure 2 . DETAILED DESCRIPTION

[0105] The present invention is not limited to the following examples. In addition, unless otherwise specified, "parts" and "%" are by mass. The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.

[0106] Example 1 This embodiment provides a negative electrode material precursor.

[0107] The negative electrode material precursor of this embodiment contains low-crystalline carbon, and there is a broad peak of carbon near 22° in the XRD diffraction spectrum, and the carbon Raman peak Id / Ig ratio calculated from the Raman spectrum is 1.3; the negative electrode material precursor provided in this embodiment has a narrow particle size distribution, Dv50 is 7.9μm, Dv99 is 17μm, Dn10 / Dv10=0.73 The negative electrode material precursor provided in this embodiment has low internal closed pores, and the SEM-CP photo statistics show that the closed pore area with a diameter >100nm accounts for <3%; the carbon, silicon, and oxygen contents of the negative electrode material precursor are 96%, 0.06%, and 1%, respectively; the negative electrode material precursor has a high BET 2018 and a high GM value (17.9).

[0108] The negative electrode material precursor provided in this embodiment is mainly prepared by the following steps: First, weigh 5kg of phenolic resin (carbon source precursor) and grind it to less than 200um by ball milling. Then put it into a crucible and place it in a box furnace. 1G1, carbonization step, inert gas nitrogen is introduced into the reaction chamber of the box furnace equipped with the carbon source precursor, the flow rate of inert gas nitrogen is 1L / min / kg, i.e. 5L / min, and the reaction chamber is heated to 300℃ for polymerization for 2h, and then the reaction chamber is heated to 1TG1, 1TG1 is 900℃, and carbonization cracking reaction is carried out, and 1TG1 is kept warm for 4h. During this process, the surface pressure of the reaction chamber is 0.1kpa-20kpa; after the pyrolysis reaction, 2.5kg of the negative electrode material precursor intermediate is obtained; this intermediate 2.5kg is subjected to air flow crushing (flat air flow mill, i.e. disc air flow mill) and air flow classifier classification, and the test particle size Dn10 / Dv10=3.4 / 4.7=0.72, Dv50: 7.8 microns.

[0109] 1G2: Activation step, transferring the carbonized and crushed precursor intermediate to the reaction chamber of a rotary kiln reactor, setting the rotary kiln speed to 1 rpm, introducing nitrogen into the rotary kiln chamber at a nitrogen flow rate of 1.8 L / min / kg, i.e., 4.5 L / min, and heating the rotary kiln reaction chamber to 950°C. After keeping the temperature for 5 hours, stop introducing nitrogen, and introduce carbon dioxide into the reaction chamber at a carbon dioxide flow rate of 1.8 L / min / kg, i.e., 4.5 L / min. Keep the temperature at 950°C for 28 hours to activate and form pores in the pyrolytic carbon. During this process, the surface pressure of the reaction chamber is 0.1kpa-20kpa; after activation for 28h, the carbon dioxide is switched to nitrogen, and the nitrogen flow rate is 1.8L / min / kg, i.e., 4.5L / min, and the heating is stopped. After the sample cools to room temperature, 1kg of negative electrode material precursor is obtained after weighing; the obtained negative electrode material precursor is subjected to powder test, and the test results are shown in Table 1; from the argon adsorption and desorption test results, the negative electrode material precursor prepared in the embodiment has a high specific surface area of ​​2018m 2 / g, the highest pore volume is 1.13cc / g, the highest GM is 17.9, the appropriate mesopore ratio is 36% of pores of 2-50nm, the micropore ratio is 64% of pores of <2nm; the appropriate conductivity, as well as TG weight loss and water content (20mg / g). A certain water content increases the polarity of the porous carbon precursor, which is conducive to guiding silane into the pores for deposition. The contents of oxygen, nitrogen, and hydrogen are 1%, 0.2%, and 0.1%, respectively, which is also conducive to guiding silane into the pores for deposition. .

[0110] Example 2 The difference between this embodiment and embodiment 1 is that, when preparing the negative electrode material precursor, the air flow crushing classification parameters are adjusted, and the particle size distribution of the prepared negative electrode material precursor is Dv50 of 7.8 μm, Dv99 of 18 μm, and Dn10 / Dv10=0.24; the preparation method and its step parameters refer to embodiment 1; the obtained negative electrode material precursor is subjected to powder test, and the test results are shown in Table 1; Example 3 The difference between this embodiment and embodiment 1 is that: When preparing the precursor of the negative electrode material, the carbon source precursor is selected from commercially available phenolic resin balls, the activation step adopts an alkali activation method, and the raw material adopts a commercially available KOH reagent, as follows; the rest of the preparation method and its step parameters refer to Example 1; Commercially available phenolic resin balls have a Dv50 of 6.7 microns and a Dn10 of 1.2 microns. First, weigh 5 kg of phenolic resin ball carbon source precursor, put it into a dry pot and place it in a box furnace for carbonization and pyrolysis. The carbonization step is based on Example 1 to obtain 2.5 kg of the negative electrode material precursor intermediate; In the activation step, 100 g of the negative electrode material precursor intermediate and the alkaline activator KOH reagent (KOH purity 85%) were fully mixed in a mass ratio of 1:3, placed in a crucible and transferred to the reaction chamber of a rotary kiln reactor, the rotary kiln speed was set to 1 rpm, inert gas nitrogen was introduced and the temperature was raised to 750°C, the nitrogen flow rate was 5 L / min / kg, i.e. 0.5 L / min, and an activation reaction was carried out, and the temperature was kept at 750°C for 0.75 h.

[0111] During this process, the surface pressure of the reaction chamber is 0.1kpa-20kpa; Passivation step, then, the gas introduced into the rotary kiln reaction chamber is switched to CO2-containing gas for passivation treatment for 2 hours, the CO2-containing gas flow rate is 5L / min / kg, i.e. 0.5L / min, and after 2 hours of passivation treatment, it is switched to nitrogen for cooling; during this process, the surface pressure of the reaction chamber is 0.1kpa-20kpa; The above-mentioned passivated intermediate was pickled, washed with water, and dried to remove excess metal impurities and excess water to obtain a negative electrode material precursor. The obtained negative electrode material precursor was subjected to powder testing. The test results are shown in Table 1. The metal impurity element content was 35ppm and the water content was 5mg / g. The specific surface area of ​​the negative electrode material precursor is 2019m 2 / g, with a pore volume of 0.95 cm 3 / g, the proportion of micropores is significantly increased to 99%, and the GM is 21.3.

[0112] Example 4 The difference between this embodiment and embodiment 1 is that when preparing the negative electrode material precursor, the carbonization temperature is 1200°C and the air flow crushing parameters are adjusted; the preparation method and its step parameters refer to embodiment 1. The obtained negative electrode material precursor is subjected to powder testing, and the test results are shown in Table 1; the carbon, silicon and oxygen contents of the negative electrode material precursor are 97%, 0.06% and 0.5% respectively; Example 5 The difference between this embodiment and embodiment 1 is that when preparing the negative electrode material precursor, the activation gas is replaced with water vapor, the activation holding time is changed to 22h, and the remaining preparation methods and step parameters thereof refer to embodiment 1; the obtained negative electrode material precursor is subjected to powder test, and the test results are shown in Table 1; the specific surface area of ​​the negative electrode material precursor is 1870m 2 / g, the pore volume increased significantly to 1.5cm 3 / g, the proportion of mesopores increased significantly to 42%, and GM was 12.5. The Id / Ig ratio of the carbon Raman peak calculated from the Raman spectrum was 1.55.

[0113] Example 6 The difference between this embodiment and embodiment 1 is that the activation time is 12 hours; the rest of the preparation method and its step parameters refer to embodiment 1; the specific surface area of ​​the negative electrode material precursor is 1300m 2 / g, pore volume is 0.43cc / g, micropore ratio is significantly increased to 99.8%, GM is significantly increased to 30.2. The carbon Raman peak Id / Ig ratio calculated from the Raman spectrum is 1.3. When preparing the composite material, the silicon deposition time is shortened to 3.7h.

[0114] Example 7 The difference between this embodiment and embodiment 5 is that commercially available coconut shell carbon is used for steam activation to prepare the negative electrode material precursor, and the activation time is shortened to 15 hours; the remaining preparation methods and step parameters thereof refer to embodiment 5; the obtained negative electrode material precursor is subjected to powder test, and the test results are shown in Table 1; the SEM-CP photo statistics show that the area of ​​closed pores with a diameter >100 nm accounts for <15%; the carbon, silicon, and oxygen contents are 95%, 0.1%, and 3.8%, respectively; the carbon Raman peak Id / Ig ratio calculated from the Raman spectrum is 1.4.

[0115] Example 8 The difference between this embodiment and embodiment 1 is that: 1) independently synthesizing a narrow distribution phenolic resin microsphere carbon source precursor, the specific synthesis comprises the following steps, 2) the activation time is shortened to 22h, and the remaining preparation methods and step parameters thereof refer to Example 1; In this embodiment, phenolic resin microspheres were prepared by precipitation method. 1610g of resorcinol and 1020g of urotropine were fully mixed with 16L of deionized water and stirred at 600 rpm until completely dissolved; then the temperature was raised to 85°C, and the reaction was carried out at a constant temperature for 7 hours before spray drying. The collected material was 1900g. After carbonization activation, the particle size of the negative electrode material precursor was tested, and the results were Dv50 was 4.9μm, Dv99 was 9.7μm, and Dn10 / Dv10=0.67.

[0116] Example 9 The difference between this embodiment and embodiment 1 is that: 1) In the activation step, a fluidized bed reactor was used and the bottom stirring blade speed was set to 100 rpm. 2) The carbon dioxide flow rate was changed to 0.4 L / min / kg, i.e., 1 L / min; 3) The temperature was changed to 910° C. and kept for 24 h to activate and pore the pyrolytic carbon; the remaining preparation methods and step parameters were referred to Example 1; The materials obtained in Examples 1-9 and Comparative Examples 1-6 were used to prepare composite negative electrode materials. 1P1, take 20g of the negative electrode material precursor obtained above and put it into a tubular rotary furnace, introduce nitrogen into the tubular rotary furnace containing the negative electrode material precursor, set the speed to 1 rpm, the nitrogen flow rate to 5L / min / kg, i.e. 0.1L / min, and heat it to 1T1, 1 is 410℃, keep it warm for 1h, stop introducing nitrogen, introduce a mixed gas of monosilane and diluent nitrogen into the reaction chamber containing the negative electrode material precursor, the volume ratio of monosilane gas and nitrogen is 1:1, and introduce it into the tubular furnace at a flow rate of 7.5L / min / kg, i.e. 0.15L / min, for silicon deposition for 4.5h, then switch the mixed gas of monosilane and nitrogen back to nitrogen, with a flow rate of 5L / min / kg, and pass nitrogen for 30min to remove monosilane in the reaction chamber. A composite negative electrode material intermediate with deposited silicon material is obtained; the surface pressure of the reaction chamber is 0.1kPa to 20kPa; 1P2, then, the 1P1 tubular rotary kiln reaction chamber is heated to 690°C and kept warm for 2 hours, and then the temperature is lowered to 1T2, 1T2 is 500°C, and after keeping warm for 1 hour, the nitrogen is stopped, and a mixed gas of acetylene and nitrogen is introduced into the reaction chamber of 1P1, the volume ratio of acetylene gas and nitrogen is 1:1, and the flow rate is 5L / min / kg, i.e. 0.1L / min, for vapor deposition of carbon, the deposition time is t2, t2 is 5h; then the introduction of the mixed gas of acetylene and nitrogen is stopped, and switched to nitrogen gas introduction, the flow rate is 5L / min / kg, i.e. 0.1L / min, until the reaction product is cooled to room temperature, and a composite negative electrode material is obtained; the surface pressure of the reaction chamber is 0.1kPa to 20kPa. The obtained composite negative electrode material is subjected to powder testing, electrochemical testing, full battery assembly and testing, and the test results are shown in Table 1; Table 1-1

[0117] Table 1-2

[0118] Table 1-3

[0119] Comparative Example 1 In this comparative example, commercially available coconut shell porous carbon was used as the precursor of the negative electrode material to prepare the composite negative electrode material, and the powder and battery performance were tested, referring to Example 1.

[0120] Comparative Example 2 The difference between this comparative example and Example 1 is that the activation temperature is 1300° C.; the rest of the preparation method and its step parameters refer to Example 1.

[0121] Comparative Example 3 The difference between this comparative example and Example 1 is that the carbonization temperature is 2500° C.; the rest of the preparation method and its step parameters refer to Example 1.

[0122] Comparative Example 4 The difference between this comparative example and Example 1 is that the negative electrode material precursor is changed to a carbon aerogel carrier; the rest of the preparation method and its step parameters refer to Example 1.

[0123] Comparative Example 5 The difference between this comparative example and Example 1 is that the negative electrode material precursor is changed to a carbon nanotube carrier; the remaining preparation methods and step parameters are referenced to Example 1. Comparative Example 6 In this comparative example, commercially available porous graphite was used to prepare a composite negative electrode material, and the powder and battery performance were tested, referring to Example 1.

[0124] Table 1 Specific synthesis conditions and test results of the embodiments and comparative examples By comparing Examples 1-2, it can be seen that in the preparation process of the negative electrode material precursor, adjusting the airflow crushing and grading parameters can optimize Dn10 / Dv10. By adopting the crushing and grading parameters of Example 1, a higher Dn10 / Dv10 ratio can be achieved, and the Dn10 / Dv10 ratio of the composite negative electrode material is also improved accordingly, thereby improving the expansion, cycle and initial efficiency of the negative electrode material.

[0125] This is because the Dn10 / Dv10 ratio increases, the proportion of high-activity particles decreases, the reaction activity with the electrolyte decreases, the interface stability increases, the cycle performance improves, less SEI is formed during the first charge, and the first efficiency is higher. At the same time, the by-products during the cycle are also reduced, the increase in electrode thickness caused by by-products is reduced, and the expansion is also significantly improved.

[0126] By comparison with Examples 1-3, in Example 3, during the preparation of the negative electrode material precursor, an alkaline activation method is used to obtain a negative electrode material precursor with ultra-high microporosity and higher GM. After the same composite negative electrode material preparation process is carried out, a composite negative electrode material with a small Si (111) grain size, a low DQ / DV primary and secondary peak intensity ratio, a suitable carbon Raman peak ratio ID / IG excellent structure can be obtained, so that the pole piece expansion, cycle and rate performance of this composite negative electrode material are better; at the same time, the more regular spherical morphology improves the tap density, so that the composite negative electrode material has good pressure resistance, the particles are not easy to break during cold pressing and charging and discharging, and the structural stability is better, which is conducive to interface stability, reducing electrolyte consumption and improving cycle performance; By comparison of Examples 1-4, when preparing the negative electrode material precursor in Example 4, the carbonization temperature is 1200°C, the carbon disorder degree after high temperature treatment is reduced, the Raman Id / Ig ratio is reduced, and the activation effect is reduced. At the same time, due to the high temperature treatment, the silicon and oxygen contents are reduced, which is not conducive to the activation effect. Therefore, the BET and pore volume of the prepared negative electrode material precursor are reduced. After the same composite negative electrode material preparation process is carried out, the gram capacity of the composite negative electrode material is reduced. This is because the silicon and oxygen contents are reduced, the affinity of silane and the negative electrode material precursor is reduced during deposition, the deposition efficiency is reduced, and the DQ / DV primary and secondary peak intensity ratio is increased, indicating that there is a small amount of silicon on the surface, so the pole piece expansion is deteriorated; By comparing Examples 1-5, in Example 5, when preparing the negative electrode material precursor, the activation gas was replaced with water vapor. Although the activation and heat preservation time was shortened, the pore volume of the negative electrode material precursor was significantly increased to 1.5 cm 3 / g, the proportion of mesopores increased significantly to 42%, and the GM was 12.5. The degree of carbon disorder increased significantly, and the carbon Raman peak Id / Ig ratio increased significantly. This shows that the water vapor activation intensity is higher. The gram capacity of the composite negative electrode material prepared from this precursor is slightly reduced, the DQ / DV primary and secondary peak intensity ratio increases, and the cycle retention rate and rate performance of the battery decrease. This shows that the GM value and the carbon Id / Ig ratio have an impact on the gram capacity of the composite negative electrode material and the cycle retention rate and rate of the battery.

[0127] By comparing Examples 1-6, the activation time of Example 6 is 12h; the specific surface area and pore volume of the negative electrode material precursor are reduced accordingly, but the micropore ratio is significantly increased to 99.8%, the GM is significantly increased to 30.2, and the carbon Raman peak Id / Ig ratio is basically unchanged. Due to the significant reduction in pore volume, the silicon deposition time is also shortened accordingly during the preparation of the composite material. The negative electrode material precursor under this condition can also obtain a composite negative electrode material with excellent electrical properties.

[0128] By comparing Examples 5-7, Example 7 uses commercially available coconut shell carbon for steam activation to prepare the negative electrode material precursor, and the activation time is shortened; the silicon and oxygen contents of the obtained negative electrode material precursor are significantly increased, which is beneficial to the silane deposition process and improves the gram capacity of the composite negative electrode material, but the proportion of closed pore area >100nm is also increased, which has a bad effect on the cycle performance of the composite negative electrode material; By comparing Examples 1-8, Example 8 is a synthesis of a narrowly distributed phenolic resin microsphere carbon source precursor, and the activation time is shortened; the particle size of the negative electrode material precursor is narrower and the Dn10 / Dv10 is higher. The composite negative electrode material prepared by this scheme has lower electrode rebound, higher cycle retention rate and rate performance.

[0129] By comparison with Examples 1-9, Example 9 is a fluidized bed synthesis of a narrowly distributed phenolic resin carbon source precursor, the activation temperature is reduced, and the activation time is shortened; the composite negative electrode material prepared by this scheme has low electrode rebound, high cycle retention rate and rate performance.

[0130] It can be seen from Examples 1-9 that the embodiments using the conditions of the present invention can obtain excellent negative electrode material precursors, as well as composite negative electrode materials with excellent structures and excellent electrochemical properties; Comparative Example 1 uses commercially available coconut shell porous carbon as a precursor of the negative electrode material to prepare a composite negative electrode material. The particle size of the coconut shell porous carbon is too large and the internal porosity is too high. The expansion, cycle and rate performance of the prepared composite negative electrode material are significantly worse than those of Example 1. By comparing Example 1 with Comparative Example 2, Comparative Example 2 was over-activated due to the excessively high activation temperature, and no material was obtained. It can be seen that the present invention provides a method for preparing a precursor of a negative electrode material, which has obvious advantages; By comparing Example 1 with Comparative Example 3, it can be seen from Comparative Example 3 that the carbon Raman peak ratio ID / IG of the negative electrode material precursor provided is too low, the pore structure GM is too low, and the TG weight loss is too low. The composite negative electrode material prepared from this precursor has a reduced gram capacity, and the DQ / DV primary and secondary peak intensity ratio is too high, resulting in battery expansion, cycle, and rate performance that are significantly worse than those of Example 1; Comparative Example 4 uses carbon aerogel as the precursor of the negative electrode material. Since the carbon aerogel has too high a proportion of closed pore area >100 nm, the corresponding prepared composite negative electrode material has too high a proportion of closed pore area >100 nm, which leads to a decrease in the initial efficiency, and the battery expansion, cycle, and rate performance are significantly worse than those of the embodiment.

[0131] Comparative Example 5 uses carbon nanotubes as the precursor of the negative electrode material. Since the Dn10 / Dv10 of the carbon nanotubes is too high, the proportion of the closed pore area >100nm is too high, the BET and carbon Raman peak ratios ID / IG are too low, and the Dn10 / Dv10 of the correspondingly prepared composite negative electrode material is too high, the proportion of the closed pore area >100nm is also too high, and the carbon Raman peak ratio ID / IG is too low, resulting in a decrease in the initial efficiency, and the battery expansion, cycle, and rate performance are significantly worse than those of the embodiments.

[0132] Comparative Example 6 uses porous graphite as the precursor of the negative electrode material. Since the silicon content of the porous graphite is too low, and the oxygen content and TG weight loss are too high, the battery cycle and rate performance of the correspondingly prepared composite negative electrode material are significantly worse than those of the embodiment.

[0133] By comparing Examples 1-8 with Comparative Examples 1-6, it can be seen that the negative electrode material precursor and preparation method provided by the present invention, and the battery capacity retention rate and rate performance of the corresponding composite negative electrode material have very significant advantages. The negative electrode material precursors obtained in Examples 1-9 and Comparative Examples 1-6 and the composite negative electrode materials prepared therefrom were tested and characterized for powder and pole piece performance. 1) XRD test: The test equipment used is a German Bruker X-ray diffractometer (Bruker, D8). Weigh 1.5g of the sample and put it into the groove of the glass sample holder, compact and flatten it with a glass sheet, and test it according to JJSK0131-1996 "General Rules for X-ray Diffraction Analysis", set the test voltage to 40kV, the current to 30mA, the scanning angle range to 10-80°, the scanning step length to 0.0167°, and the time for each step length to 0.24s. Import the XRD data into the jade software, set the parameters, analyze the diffraction peak of carbon near 22°, and the shape of the bun peak is amorphous carbon.

[0134] 2)>100nm closed pore area ratio test: the above negative electrode material precursor or composite negative electrode material and binder polyvinylidene fluoride (PVDF) were dissolved in N-methylpyrrolidone solvent at a mass ratio of 93:7 to prepare a slurry. The slurry was stirred and mixed and coated on the copper foil current collector. The loading amount of the composite negative electrode material was 10mg / cm 2 The coated electrode is placed in a vacuum oven and dried at 90°C for 12 hours to obtain the negative electrode; the electrode is placed on an argon ion polisher and a high-speed inert ion source is used to cut the electrode section and ion polish it. The cross section after ion cutting is observed with SEM, and the total area A of the material particles is counted, and the total area P of the closed pores with a diameter of >100nm in the particles is counted, and the proportion of the area of ​​pores >100nm = (P / A)*100%; the area of ​​the material particles is calculated, Select a particle, take the minimum circumscribed circle diameter on the particle cross section as the particle diameter D1, the area of ​​this particle A1=3.14×(D1 / 2)^2, and so on, calculate the areas of its 100 nearest neighboring particles and calculate the total area A of the material particles; Select a particle with closed pores, take the minimum circumscribed circle diameter of the pores on the particle section as the pore diameter d1, the area of ​​this pore P1=3.14×(d1 / 2)^2, and so on, calculate the pore areas of the 100 nearest neighboring particles with pore diameter d1>100nm and calculate the total area P of the pores in the material particles; closed pores are defined as the pore edge line on the particle ion polishing section is closed; closed pore SEM-CP is as follows Fig. 20 ) as shown; the minimum circumscribed circle diameter is as Fig.21 ), refer to the national standard GB_T1182-2018.

[0135] 3) Silicon content test, using inductively coupled plasma emission spectroscopy. Weigh 0.1g of the above material sample and 1.5g of KOH, mix and heat in a muffle furnace at 400℃ for 1h, transfer the treated mixture to a beaker, and soak it in 98℃ deionized water for 2h. Filter the soaked solution to remove the residue and transfer it to a volumetric flask, add deionized water to make it 100mL. Add the fixed solution to the atomization chamber, pump at 1.3L / min, and test.

[0136] 4) Particle size test: The particle size distribution of the powder was tested by laser diffraction method, with specific reference to the national standard GB / T19077-2016 and the testing equipment Malvern 3000. Take 0.2g of the above material and put it into a beaker, add 20mL of deionized water and 5 drops of surfactant, transfer to an ultrasonic cleaner for ultrasonic dispersion for 5min to obtain a dispersion. The dispersion was tested using MasterSizer3000 to obtain the particle size distribution diagram of the sample, as well as the volume distribution parameters Dv10, Dv50, Dv90, Dv99 and the number distribution parameters Dn10, Dn50, Dn90, Dn99. Dv50 means that the diameter of particles accounting for 50% of the total volume of the sample is less than this value. And so on. Dv99 means that the diameter of particles accounting for 90% of the total sample volume is less than this value. Dn10 means that the diameter of particles accounting for 10% of the total number of sample particles is less than this value. And so on. Dn99 means that the diameter of particles accounting for 90% of the total number of sample particles is less than this value. 5) BET test, using nitrogen adsorption and desorption method to test the specific surface area of ​​the above materials, refer to the national standard GB / T19587-2017 for details. Weigh 2g of the above material powder into the test sample tube and degas at 200°C for 2h. After degassing, the sample tube is transferred to the test bench for testing. The adsorbent is high-purity nitrogen, and adsorption and desorption are performed at liquid nitrogen temperature and data are collected; the specific surface area is calculated by the multi-point BET method.

[0137] 6) BET, pore volume, and micro-mesopore ratio tests were conducted using a high-precision adsorption instrument (Li-Chem Lianke) to perform adsorption-desorption curve tests. The adsorption-desorption gas was Ar gas, and the P / P0 measurement range was 0.00000001-0.99. Weigh 0.1g of the above material powder into the test sample tube and degas at 200°C for 2h. After degassing, the sample tube was transferred to the test bench for testing. The adsorption-desorption curve data collected were used to calculate BET and pore volume using the IporeDFT software. The micropore ratio and mesopore ratio were calculated using the pore size and pore volume data. Micropore ratio = (pore volume <2nm / total pore volume) * 100%; mesopore ratio = (pore volume 2-50nm / total pore volume) * 100%; In order to obtain a smoother pore size-pore volume increment change distribution curve, the pore volume increment change value can be taken at fixed intervals, such as the first, second , the 3rd, 4th, 5th, 6th, ... to the nth pore volume increase data are PV1, PV2, PV3, PV4, PV5, PV6, ... to PVn, the first, 2nd, 3rd, 4th, 5th, 6th, ... to the nth data of pore volume increase change are (PV5-PV1), (PV6-PV2), (PV7-PV3), (PV8-PV4), (PV9-PV5), (PV10-PV6), ... to (PVn+4-PVn); 7) Raman test, the test equipment is HoribaJobin-YvonLabRAMHR800 spectrometer, the light source is 532nm, and the test wavelength range is 0cm-1~4000cm-1. Take a small amount of powder and evenly disperse it on the sample table, adjust the equipment parameters, analyze the sample area of ​​100μm*100μm, and obtain the Raman spectrum; calculate the intensity ratio of the peaks at ~1340cm-1 and ~1600cm-1 of the carbon material from the Raman spectrum of the composite negative electrode material. Count the intensity ratios of 100 regions and calculate their average value to obtain the ID / IG of carbon. This intensity ratio reflects the degree of disorder of the carbon material. A higher ratio represents the presence of higher disordered carbon, which is beneficial to improve the strength of the porous carbon carrier and thus improve the stability of the composite negative electrode material in the cycle.

[0138] The same method is used to calculate the intensity ratio of the peaks at ~125cm-1 and ~465cm-1 of the silicon material to obtain the ID / IG of the silicon material.

[0139] 8) Carbon content test, use high-frequency infrared carbon and sulfur analyzer (Shanghai Dekai HCS-140) to test samples. Its working principle is to use the characteristics of CO2 and SO2 at 4.26μm and 7.4μm respectively, which have strong characteristic absorption bands. By measuring the gas absorption light intensity and analyzing the CO2 and SO2 content, the percentage of carbon and sulfur elements in the tested sample can be indirectly determined. Take 0.5g of the above material sample and input it into the computer, then heat the sample in a high-frequency furnace under oxygen-rich conditions until it burns, so that carbon is oxidized into CO2 gas. The carbon content in the sample can be obtained by analysis and calculation.

[0140] 9) Oxygen, nitrogen and hydrogen content test: high-temperature melting method is adopted for extraction, inert atmosphere, low voltage and high current are added between the upper and lower electrodes of the pulse electrode furnace to heat the sample, and the oxygen in the sample reacts with the carbon in the graphite crucible to generate CO or CO2, which is then detected by the non-dispersive infrared detector NDIR; similarly, the hydrogen in the sample is first generated into hydrogen gas, then oxidized by CuO to H2O, and then kept at a constant temperature of 120°C, and tested by the water detector NDIR; the nitrogen in the sample is detected by thermal conductivity method TCD. The detected gas is converted into a signal corresponding to the corresponding concentration, and the final measurement result is obtained by signal processing. Refer to the national standard GB / T 14265-2017, test equipment HORIBA, EMGA-830, sample size 0.05g. The test results are expressed in mass percentage.

[0141] 10) Tap density test, tap density is referred to as TD, and the test equipment used is Dandong Better BT303. Weigh 20g of sample and put it into a 30ml measuring cylinder. Test according to GB / T24533-2019, set the vibration frequency to 100-300 rpm, amplitude to 3±0.1mm, vibration times to 5000 times, frequency to 250±15 times / min, and calculate the tap density according to the company's ρ=mV, the unit is g / cm³.

[0142] 11) Powder density test, take 5g sample and test it with powder compaction density instrument (model, Tianjin Bojun BJ-24); first, put a metal disc into the bottom of the special mold, then put 5g powder into the special mold, and then put a metal disc on the powder so that the powder is located between the two metal discs, put the mold on the powder compaction density instrument, put a metal cylinder on the top disc of the mold, set the pressure parameter to 5T, the pressure displacement rate parameter to 20mm / min, the pressure holding time to 60s, the pressure relief displacement rate parameter to 20mm / min, record and calculate the thickness of the sample after pressure relief, and calculate the volume of the powder after pressure relief. Finally, calculate according to the density formula to obtain the 5T powder compaction density PD.

[0143] 12) Powder conductivity test, test reference standard GB / T 30835-2014, resistivity test instrument is HIOKI3563, electronic pressure tester, electronic balance, weigh 3.5g sample and place it in the test mold of the electronic pressure tester, gently vibrate the vibration balance, then place the gasket on the mold on the sample, connect the mold to the resistivity test, constant pressure to 3500kg for 2min, read the sample height and the value of the resistance tester. Conductivity calculation formula, σ=1000*h(S*R), σ is powder conductivity, unit μS / cm, h is sample height, unit cm, S is sample bottom area, unit 3.14cm², R is sample resistance, KΩ.

[0144] 13) Thermogravimetric (TG) test, the test reference standard GB / T 13464-2008, the analysis method of thermal stability of materials, the test instrument is German NETZSCH STA449F3, the atmosphere is high-purity nitrogen, the sample weight is 0.5g, the heating rate is 5℃ / min, and the test temperature range is room temperature to 800℃.

[0145] 14) Sphericity test: The above negative electrode material precursor or composite negative electrode material and binder polyvinylidene fluoride (PVDF) were dissolved in N-methylpyrrolidone solvent at a mass ratio of 93:7 to prepare a slurry. The slurry was stirred and mixed and coated on the copper foil current collector. The loading amount of the composite negative electrode material was 10 mg / cm 2 The coated electrode is placed in a vacuum oven and dried at 90°C for 12 hours to obtain the negative electrode; the electrode is placed on an argon ion polisher and a high-speed inert ion source is used to cut the electrode section and ion polish it. The cross section after ion cutting is observed with SEM, and the ratio Q of the long side L to the short side W on the particle section is calculated, Q = (W / L) * 100%; sphericity calculation: Select a particle, take the minimum circumscribed ellipse on the particle cross section, record the major axis of the ellipse as the long side L1, and the ellipse as the short side W1. The sphericity of this particle is recorded as Q1= (W1 / L1)*100%. Similarly, calculate the Q values ​​of the 100 nearest neighboring particles with a major axis diameter greater than 3μm and calculate their average value to obtain the sphericity of the material particle. 15) H2O content test: Karl Fischer coulometric method is used for testing, with specific reference to national standard GB / T11133-2015, and testing equipment 831-885 coulometric moisture meter. Take 0.2g of the above material, heat it and purge it into the titration cup with dry gas to titrate the water vapor. The test conditions are 170℃ 300s, gas flow rate 40-60ml / min. If the moisture content is high, it will exceed 300s until the set conditions are reached. Convert the result into the water content of the sample. The unit is mg / g.

[0146] The electrochemical performance of the composite negative electrode materials prepared from the negative electrode material precursors obtained in Examples 1-9 and Comparative Examples 1-6 was tested and characterized. 1) The first efficiency test of composite negative electrode material gram capacity

Electrode preparation

[0147]

Electrolyte preparation

[0148] [Preparation of isolation film] A commercially available polyethylene (PE) porous polymer film with a thickness of 7 μm was used as the isolation film and punched into 10 mm small discs.

[0149]

Battery assembly

[0150]

Battery test

[0151] 2) 0.9V capacity ratio test of composite negative electrode material, 0.9V capacity ratio = (specific capacity of the first charge to 0.9V / specific capacity of the first charge) × 100% 3) DQ / DV primary and secondary peak intensity ratio test of composite negative electrode materials The first charge and discharge curve of the composite negative electrode material is obtained by the blue electric test, with the charge and discharge specific capacity as the horizontal axis and the voltage as the vertical axis. In the present invention, the first cycle charge specific capacity is recorded as Q and the voltage is recorded as V. The data obtained by differential calculation is used as the horizontal axis, and the voltage V is used as the vertical axis to obtain the DQ / DV-V differential capacity curve, such as Fig. 9 As shown; to obtain a smoother curve, the interval difference method can be selected, for example, the first point of DQDV = (Q10-Q1) / (V10-V1), the second point of DQDV = (Q11-Q2) / (V11-V2), the third point of DQDV = (Q12-Q3) / (V12-V3), and so on. Among them, Q1, Q2, Q3, Q10, Q11, Q12 are the abscissa specific capacity values ​​of the first point, the second point, the third point, the tenth point, the eleventh point, and the twelfth point of the first cycle charge specific capacity-voltage curve, and V1, Q2, Q3, Q10, Q11, Q12 are the ordinate voltage values ​​of the first point, the second point, the third point, the tenth point, the eleventh point, and the twelfth point of the first cycle charge specific capacity-voltage curve. From Fig. 9 As can be seen from the figure, the characteristic peak at 0.24V-0.35V is the main peak, the highest peak intensity in this voltage range is recorded as I1, and the characteristic peak at 0.38V-0.45V is the secondary peak, the highest peak intensity in this voltage range is recorded as I2, and the lowest peak intensity between 0.24V and 0.45V is recorded as I3. The main and secondary peak intensity ratio of DQ / DV = (I2-I3) / (I1-I3) From the publicly available data, different characteristic peaks correspond to different electrochemical reactions. The characteristic peak of I1 represents the highest value of the delithiation reaction of amorphous LixSi, and the characteristic peak of I2 represents the highest value of the delithiation reaction of crystalline Li15Si4. The more delithiation reactions there are, the higher the corresponding peak intensity. Since the expansion ratio of the Si lattice caused by the formation of Li15Si4 is very large, it is not conducive to the stability of the lattice and the stability of the electrolyte. The DQ / DV primary and secondary peak intensity ratio needs to be controlled within a certain range, and the preferred range is <1. A low primary and secondary peak intensity ratio is conducive to the improvement of the cycle performance of the composite negative electrode material.

[0152] 4) Fully charged electrode rebound (withdrawal), the difference between the withdrawal assembly and 1) the first efficiency test of composite negative electrode material gram capacity is that the composite negative electrode material is replaced with a mixed negative electrode active material during electrode preparation (the above composite negative electrode material is mixed with commercially available artificial graphite in a certain proportion to obtain a mixed negative electrode active material with a specific capacity of 750mAh / g). When the battery is tested, the additional process is: 0.1C discharge to 0.005V, 0.05C discharge to 0.005V, let stand for 10min, 0.01C discharge to 0.005V, let stand for 10min, and end the test with full charge; the rest of the steps refer to 1) the first efficiency test of composite negative electrode material gram capacity. Take the tested buckle battery, disassemble it, take out the negative electrode sheet and measure the thickness of 5 positions in the center of the electrode sheet with a spiral micrometer. Measure 5 buckles in the same way to get 25 thickness data, and calculate the average value as C2; Full charge electrode sheet rebound = (C1 / C2) × 100%, C1 is the thickness of the negative electrode sheet of 5 tons cold pressing in the preparation of the electrode sheet; 5) Full battery cycle performance test and rate performance test [Preparation of negative electrode sheet] The above-mentioned composite negative electrode material is mixed with commercially available artificial graphite in a certain proportion to obtain a mixed negative electrode active material with a specific capacity of 450mAh / g. The mixed negative electrode active material, carbon nanotubes, lithium carboxymethyl cellulose, and lithium polyacrylate are mixed in a mass ratio of 93.2:0.4:1.4:5 to prepare a slurry. After mixing, an appropriate amount of solvent deionized water is added to obtain a negative electrode slurry under the action of a Ross mixer. The solid content of the negative electrode slurry is 41wt%, and the viscosity is 1500-5000mpa*S; the stirred and mixed slurry is transferred to the silo of the coating machine, and the slurry is coated on the copper foil current collector with a transfer coating machine. The parameters of the coating machine and the series-connected drying machine are adjusted to obtain a mixed negative electrode active material with a loading amount of 8.1mg / cm 2 Double-sided coated electrode; the electrode is transferred to a vacuum oven and dried under vacuum conditions at 90°C for 12 hours; then it is transferred to a cold press to obtain a cold-pressed electrode with a compaction density of 1.7g / cc, and the cold-pressed electrode is transferred to a slitting machine for slitting, and finally a negative electrode with a coating area width of 70mm × length of 360mm is obtained; then the electrode ear welding and glue pasting processes are carried out.

[0153] [Preparation of positive electrode sheet] The positive electrode material is 4.5V lithium cobalt oxide with a gram capacity of 180 mAh / g. The positive electrode active material lithium cobalt oxide, conductive carbon (SuperP) and binder polyvinylidene fluoride (PVDF) are dissolved in an N-methylpyrrolidone solvent system at a mass ratio of 96:2:2. The amount of solvent added is appropriately adjusted, and the positive electrode slurry is obtained under the action of a stirrer. The solid content of the positive electrode slurry is 65% and the viscosity is 4000-10000 mPa.s. The stirred and mixed slurry is transferred to the hopper of the coating machine, and the slurry is coated on the aluminum foil current collector with a transfer coating machine. In order to achieve a designed excess capacity of 0.08 of the negative electrode to the positive electrode, the parameters of the coating machine and the drying machine are adjusted to obtain a loading amount of 18.2 mg / cm of lithium cobalt oxide material. 2 Double-sided coated pole piece; The electrode piece is transferred to a vacuum oven and dried under vacuum conditions at 90°C for 12 hours; then it is transferred to a cold press to obtain a cold-pressed electrode piece with a compaction density of 4.2g / cc, and the cold-pressed electrode piece is transferred to a slitting machine for slitting, and finally a positive electrode piece with a coating area width of 65mm × length of 355mm is obtained; then the electrode ear welding and glue sticking processes are carried out.

[0154] [Electrolyte preparation] The electrolyte was prepared by mixing lithium salt LiPF6 and non-aqueous solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): fluoroethylene carbonate (FEC)) = 20:30:20:25:5, mass ratio) in a mass ratio of 8:92.

[0155] [Preparation of isolation film] Use commercially available polyethylene (PE) porous polymer film as the substrate layer with a thickness of 7μm. Put water, inorganic particulate aluminum oxide and adhesive into a stirrer and mix them evenly to obtain a slurry for coating. Evenly coat one side of the substrate layer PE to a suitable thickness, and then put it into an oven for drying to obtain the isolation film of the present invention. After being slit according to the designed size, it enters the winding machine; [Battery assembly] The negative electrode sheet, separator, and positive electrode sheet are placed in the winding machine in order, with the separator placed between the positive and negative electrode sheets, and the electrode roll is obtained after winding. The electrode roll is placed in a punched aluminum-plastic film packaging bag, and after the top seal is completed, it is transferred to a drying oven and vacuum dried at 140°C for 12 hours; the dried top-sealed electrode roll is transferred to the liquid injection machine in the drying room, and the prepared electrolyte is injected at a rate of 1.52g / Ah; after vacuum packaging, standing, formation, degassing, trimming and other processes, a lithium-ion secondary battery is obtained.

[0156]

Battery test

[0157] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and the scope of protection of the present invention is defined by the attached claims, description and their equivalents.

Claims

1. A precursor of a negative electrode material, which contains low-crystalline carbon and has an Id / Ig ratio of the carbon Raman peak ranging from 0.7 to 1.7; the precursor of the negative electrode material is characterized in that, 1) The Dv50 of the precursor of the negative electrode material is from 3 μm to 15 μm, the Dv99 is from 6 μm to 30 μm, and Dn10 and Dv10 satisfy the following relationship: 0.1 ≤ Dn10 / Dv10 ≤ 0.9; 2) The precursor of the negative electrode material has a high BET of 1000 - 4000 and a high GM value (12 - 32); 3) The mass proportion range of silicon element in the precursor of the negative electrode material is 0.001% ≤ X ≤ 5%, the proportion range of carbon element is 70% ≤ Y < 100%, and the proportion of oxygen element is 0.1% - 10%.

2. The negative electrode material precursor according to claim 1, characterized in that: It has a low proportion of closed pore area, and the proportion of closed pore area > 100 nm is < 20%.

3. The negative electrode material precursor according to claim 1, characterized in that: The sphericity of the precursor particles of the negative electrode material is preferably 50% - 97%.

4. The negative electrode material precursor according to claim 1, characterized in that: The powder conductivity is 0.001 - 20 S / cm.

5. The negative electrode material precursor according to claim 1, characterized in that: The tap density of the precursor of the negative electrode material is TD, and the preferred range of TD is 0.1 < TD < 0.8 g / cc. The powder compaction density is PD, and the preferred range of PD is 0.3 < PD < 1.0 g / cc. The true density is preferably in the range of 1.5 - 2.2 g / cc.

6. The negative electrode material precursor according to claim 1, characterized in that: The thermal weight loss TG of the precursor of the negative electrode material is -13 to 2%, and the mass proportion range of H2O in the precursor of the negative electrode material is 0.1 - 120 mg / g.

7. The negative electrode material precursor according to claim 1, characterized in that: BET is 1000-4000m 2 / g, the pore volume is 0.4-2.0cc / g, and the pore size of 0.3-2nm accounts for >50%.

8. The composite negative electrode material prepared from the negative electrode material precursor according to claim 1, characterized in that: The mass proportion range of silicon element in the composite negative electrode material is 10% ≤ X ≤ 60%, the proportion range of carbon element is 30% ≤ Y ≤ 80%, and the proportion of oxygen element is 0.1% - 15%.

9. The composite negative electrode material prepared from the negative electrode material precursor according to claim 8, characterized in that: The specific capacity of the composite negative electrode material is 600 - 2500 mAh / g, the first efficiency is 80% - 96%, and the ratio of the capacity of the first de-lithiation to 0.9 V to the capacity of the first de-lithiation to 2.0 V of the composite negative electrode material is Cap, where 80% ≤ Cap ≤ 98%; the composite negative electrode material has a low DQ / DV main - to - secondary peak intensity ratio, and its range satisfies the following relational expression: DQ / DV main - to - secondary peak intensity ratio = (I2 - I3) / (I1 - I3) < 1.

10. A preparation method of a precursor of a negative electrode material, which is characterized in that, It includes at least one of gas activation method and alkali activation method. The gas activation method includes at least one of a carbonization step and an activation step. In the activation step, the flow rate of the activation gas is determined according to the weight of the carbon source precursor in the reaction chamber, The flow rate of the activation gas is 0.2 - 5 L / min / kg; after the activation reaction, a precursor of the negative electrode material is obtained; The activation gas is an oxygen - containing gas, containing at least one of CO2, H2O, and O2; The alkali activation method includes a carbonization step, an activation step, and a passivation step; The alkaline activator contains KOH, the molar ratio range of the carbonization intermediate to the alkaline activator is 2 - 0.2, and the passivating agent is an oxygen - containing gas, containing at least one of CO2, H2O, and O2.

11. The method for preparing a negative electrode material precursor according to claim 10, characterized in that: The carbon source precursor includes a high molecular polymer, including but not limited to polyacrylonitrile, phenolic resin, melamine resin, epoxy resin, urea-formaldehyde resin, polyester resin, polyamide resin, polyimide resin, polycarbonate, and acrylonitrile copolymer; the biomass carbon source includes but is not limited to coconut shell, fruit shell, fruit core, oil tea shell, wood, cellulose, straw, bamboo, walnut shell, sugar, and starch; and the fossil raw material carbon source includes but is not limited to at least one of asphalt, coal, and petroleum.

12. The method for preparing a negative electrode material precursor according to claim 10, characterized in that: The carbonized intermediate of the carbon source precursor exists in a fluidized state or an expanded state under the action of the airflow or the baffle or other components inside the cavity, and the volume of the dense phase region is 1.2 to 2.5 times the volume of static accumulation.

13. A method for preparing a silicon-carbon composite negative electrode material using the negative electrode material precursor according to claim 1, characterized in that: The method comprises a silicon deposition method, wherein a silicon source gas is introduced into a reactor containing the negative electrode precursor for pyrolysis deposition; It also includes passivation treatment and coating treatment after silicon deposition to obtain the composite negative electrode material; The silicon source gas comprises at least one of monosilane, disilane, silicon vapor, trichlorosilane and dichlorosilane; The dilution gas comprises at least one of hydrogen, argon and nitrogen; The carbon source gas includes but is not limited to hydrocarbon gas for carbon deposition treatment; The hydrocarbon gas includes but is not limited to at least one of methane, ethane, propane, ethylene, propylene and acetylene; it also includes but is not limited to introducing a mixed gas containing hydrocarbon gas and inert gas for coating treatment, wherein the inert gas includes but is not limited to at least one of argon and nitrogen; the dilution gas contains at least one of hydrogen, argon and nitrogen.

14. The method for preparing a negative electrode material precursor according to claim 10, characterized in that: The carbonization and activation heat treatment device uses a reaction device with a heating mechanism, including but not limited to at least one of a fluidized bed reactor, a rotary kiln, a vertical moving layer reactor, a tunnel furnace, an intermittent furnace, a push plate kiln, a roller kiln, a box furnace and a tubular furnace.

15. A composite negative electrode material, used in combination with a carbon-based negative electrode material previously known as a negative electrode active material for a lithium-ion secondary battery, as required, characterized in that: The ratio of the composite negative electrode material to the carbon-based negative electrode material is 0.1:99.9 to 80:20, preferably 1:99.5 to 70:30, based on mass.

16. A secondary battery electrochemical device comprising a negative electrode, a positive electrode, an electrolyte and a separator, characterized in that: The negative electrode comprises a negative electrode material layer, the negative electrode material layer comprises a negative electrode active material, and the negative electrode active material comprises the negative electrode material precursor as claimed in claim 1 or the composite negative electrode material prepared by the preparation method as claimed in claim 13.

17. The secondary battery electrochemical device according to claim 16, characterized in that: In the negative electrode material layer of the negative electrode formed after the pressurization, the density of the negative electrode active material is 0.6 g / cc to 1.9 g / cc.

18. An electronic device, characterized in that: It comprises the secondary battery electrochemical device as claimed in claim 17.